Aerogel composite

KR103031868B1Active Publication Date: 2026-10-13LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020240085639
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-11-01
Filing Date
2024-06-28
Publication Date
2026-10-13
Estimated Expiration
2044-06-28
Patent Text Reader

Abstract

The present invention relates to an aerogel composite that maintains excellent thermal insulation performance even when subjected to compressive deformation due to pressure applied by various causes when applied as a thermal insulation material to batteries, electronic devices, automobiles, industrial equipment, or structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an aerogel composite and its application as an insulating material. Background Technology

[0002] Aerogels are ultraporous materials with a high specific surface area (≥500 m²) having a porosity of approximately 90.0% to 99.9% and a pore size in the range of 1 nm to 100 nm. 2 As a material with a g content, it is a material possessing excellent properties such as ultralight weight, ultra-insulating insulation, and ultra-low dielectric strength. Accordingly, active research is being conducted not only on the development of aerogel materials but also on their application as transparent and eco-friendly high-temperature insulating materials, ultra-low dielectric thin films for high-density integrated devices, catalysts and catalyst supports, electrodes for supercapacitors, and electrode materials for seawater desalination.

[0003] The biggest advantage of aerogel is that it has super-insulation properties with a thermal conductivity of 0.300 W / m·K or less, which is lower than conventional organic insulation materials such as styrofoam, and it can solve the fatal weaknesses of organic insulation materials, such as fire vulnerability and the generation of harmful gases during a fire.

[0004] Generally, aerogels are manufactured by producing a hydrogel from silica precursors such as water glass and alkoxysilane series (TEOS, TMOS, MTMS, etc.) and removing the liquid component inside the hydrogel without destroying the microstructure.

[0005] In particular, hydrophobic silica aerogel blankets, which form hydrophobic silica aerogel on fibers, are widely used in construction or industrial sites as functional thermal insulation materials that prevent corrosion caused by moisture. Additionally, they can be usefully employed as insulation, thermal insulation, or non-combustible materials for aircraft, ships, automobiles, batteries, and the like. However, when applying such silica aerogel blankets for these purposes, there has been a problem where thermal insulation performance is significantly degraded due to factors such as the collapse of the aerogel structure caused by a pressurized environment resulting from continuous thermal expansion from adjacent equipment or significant surrounding pressure during installation. The problem to be solved

[0006] One objective of the present invention is to provide an aerogel composite that can maintain a constant thermal insulation performance without significantly deteriorating even when exposed to a pressurized environment.

[0007] However, the technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem

[0008] According to one embodiment of the present invention, the aerogel composite comprises a fiber substrate and an aerogel having one or more pores, wherein when the aerogel composite is compressed by applying a pressure of 3 bar, 9 bar, or 24 bar in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression is 1.8 times or less compared to the heat transfer rate before compression, and the heat transfer rate before and after compression for the aerogel composite may satisfy the following Equation 3.

[0009] [Equation 3]

[0010] {(Thermal transmittance before and after compression (a)) - (Average value of thermal transmittances before and after compression (b))} = (Average value of thermal transmittances before and after compression (b)) XA

[0011] In the above Equation 3, the thermal transmittance before and after compression (a) refers to the thermal transmittance obtained after compressing the cross-section of the aerogel composite in the horizontal direction (transverse direction) at 0 bar, 3 bar, 9 bar, or 24 bar, and the average value of the thermal transmittances before and after compression (b) refers to the thermal transmittance of the aerogel composite without pressurization and the average value of the thermal transmittances obtained after compressing the cross-section of the aerogel composite in the horizontal direction (transverse direction) at pressure values ​​of 3 bar, 9 bar, and 24 bar.

[0012] The above A is a rational number from -0.25 to +0.25.

[0013] When the cross-section of the above aerogel composite is compressed by applying pressures of 3 bar, 9 bar, and 24 bar in the horizontal direction (transverse direction), the heat transfer rate after compression may be greater than 1 time and less than or equal to 1.8 times the heat transfer rate before compression.

[0014] When a pressure of 3 bar is applied in the horizontal direction (transverse direction) to the cross-section of the above aerogel composite, the heat transfer rate after compression may be 1.45 times or less compared to the heat transfer rate before compression.

[0015] When pressures of 3 bar, 9 bar, and 24 bar are applied in the horizontal direction (transverse direction) to the cross-section of the above aerogel composite, the compression recovery rate represented by the following Equation 1 may be 60% or more:

[0016] [Equation 1]

[0017] Compression recovery rate (%) = {(Cross-sectional thickness of aerogel composite after compression) / (Cross-sectional thickness of aerogel composite before compression)} X 100

[0018] The heat transfer coefficient obtained after compressing the cross-section of the above aerogel composite in the horizontal direction (transverse direction) at pressures of 3 bar, 9 bar, and 24 bar can satisfy the following Equation 4:

[0019] [Equation 4]

[0020] (Thermal transmittance after compression (c) - Average thermal transmittance after compression (d)) = (Average thermal transmittance after compression (d)) XB

[0021] In the above Equation 4, the thermal transmittance after compression (c) refers to the thermal transmittance obtained after compression with a pressure of 3 bar, 9 bar, or 24 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite, and the average value of the thermal transmittances after compression (d) refers to the average value of the thermal transmittances obtained after compression by applying pressures of 3 bar, 9 bar, and 24 bar, respectively, in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite.

[0022] The above B is a rational number from -0.25 to +0.25,

[0023] For the above aerogel composite, the rate of change (C) of the thermal transmittance after compression per unit applied pressure, represented by the following Equation 5, may be a rational number ranging from -0.10 to +0.10:

[0024] [Equation 5]

[0025] C = (Thermal transmittance after compression at pressure x - Thermal transmittance after compression at pressure y) / (x - y)

[0026] In the above Equation 5, x and y are each independently different pressure values, which are any one of 3 bar, 9 bar, and 24 bar (unit bar).

[0027] The above aerogel may contain pores with a pore diameter of 30 nm or less in an amount of 30% or more and 45% or less of the pore volume of the skeletal structure. The above aerogel may contain pores with a pore diameter of 0.1 nm or more and 30 nm or less in an amount of 30% or more and 45% or less of the pore volume of the skeletal structure.

[0028] The density of the above aerogel composite is 0.05 to 0.50 g / cm³ 3 It could be.

[0030] According to another embodiment of the present invention, the invention relates to an insulating member comprising an aerogel composite provided in the present invention.

[0031] The above insulating member may further include a support member located on at least one of the upper and lower surfaces of the aerogel composite. Effects of the invention

[0032] When the aerogel composite provided in the present invention is applied as an insulating material to batteries, electronic devices, automobiles, industrial equipment, or structures, etc., even if pressure is applied to the aerogel composite due to the expansion of adjacent devices or structures or other causes, causing compressive deformation, the insulating performance can be maintained at an excellent level without significantly decreasing. Specific details for implementing the invention

[0033] Hereinafter, the present invention will be described in more detail to aid in understanding the invention. In this case, terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.

[0035] According to one embodiment of the present invention, the invention relates to an aerogel composite comprising a fiber substrate; and an aerogel having one or more pores.

[0036] The above "aerogel" comprises a three-dimensional network structure in which a plurality of aerogel particles having a size of approximately 2 to 20 nm are aggregated or combined to form a plurality of open pores.

[0037] The above aerogel may be an inorganic silica aerogel formed from a silicon alkoxide-based compound or water glass as a precursor. In one example, the aerogel may be composed of silica, methylsilylated silica, dimethylsilylated silica, trimethylsilylated silica, or a mixture thereof. In another example, the aerogel may have at least some of the SiO2 on the surface of the SiO2 network structure having a bonding structure of Si-O-SiO2(CH3), Si-O-SiO(CH3)2, or Si-O-Si(CH3)3. The manufacturing process of the aerogel is described in detail below.

[0038] The "aerogel particles" mentioned above are particles in the form of individual solid units constituting the aerogel, and may be powder, beads, fine material, granules, pellets, aggregates, fibers, flakes, etc., and their shape may be spherical, hemispherical, circular, semicircular, polygonal, cubic, rod-shaped, polyhedral, irregular, etc. The aerogel particles may have an average particle size of approximately 10 to 2,000 nm, 10 to 1,500 nm, or 10 to 1,000 nm, but are not limited thereto. The average particle size may be measured by any means known to those skilled in the art, such as scanning electron microscopy, dynamic light scattering, optical microscopy, or size exclusion methods, but is not limited thereto.

[0039] The aerogel may have a skeletal structure including mesopores, and may include micropores or macropores in addition to the mesopores. Here, the "mesopore" is a pore with an average pore diameter in the range of about 2 nm to about 50 nm, the "macropore" is a pore with an average pore diameter exceeding about 50 nm, and the "micropore" is a pore with an average pore diameter less than about 2 nm. The aerogel may contain at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, at least 96%, at least 97%, at least 98%, at least 99%, or 100% mesopores of the pore volume of the skeletal structure. In one embodiment, the aerogel may include mesopores. In one specific example, the aerogel may include mesopores and micropores. The pore size may be measured by any means known to those skilled in the art, such as gas adsorption experiments, mercury infiltration, capillary flow porometry, or positron annihilation lifetime spectroscopy (PALS), but is not limited thereto.

[0040] In aerogels, pores with a diameter of 30 nm or less are not destroyed or have a low destruction rate even when the aerogel is compressed under high pressure (e.g., 37 bar or less, 33 bar or less, or 30 bar or less). Accordingly, by including pores with a diameter of 30 nm or less in a certain proportion within the aerogel, the thermal transmittance of the aerogel composite can be maintained within a certain range compared to before pressurization even under a pressurized environment.

[0041] Specifically, the aerogel may contain pores having a pore diameter of 30 nm or less, preferably 0.1 nm or more and 30 nm or less, in an amount of 25% or more, 26% or more, 27% or more, 28% or more, 29% or more, 30% or more, or 31% or more of the pore volume of the skeletal structure, and may contain 50% or less, 49% or less, 48% or less, 47% or less, 46% or less, 45% or less, 44% or less, 43% or less, 41% or less, or 40% or less, preferably 25% or more and 45% or less, 25% or more and 40% or less, 30% or more and 45% or less, or 30% or more and 40% or less, but is not limited thereto. The aerogel may contain pores having a pore diameter of 30 nm or less in an amount of 30% to 45% of the pore volume of the skeletal structure. The above aerogel may contain pores with a pore diameter of 0.1 nm or more and 30 nm or less as 30% to 45% of the pore volume of the skeletal structure.

[0042] Additionally, the aerogel may contain pores with a pore diameter greater than 30 nm in an amount of 50% or more, 51% or more, 52% or more, 53% or more, 54% or more, 55% or more, 56% or more, 57% or more, 58% or more, 59% or more, or 60% or more of the pore volume of the skeletal structure, and may contain 75% or less, 74% or less, 73% or less, 72% or less, 71% or less, 70% or less, or 69% or less, and preferably may contain 55% or more and 75% or less, 60% or more and 75% or less, 55% or more and 70% or less, or 60% or more and 70% or less, but is not limited thereto.

[0043] The porosity of the above aerogel may be 80% or more, 85% or more, 88% or more, 89% or more, 90% or more, 91% or more, 92% or more, 93% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, and preferably 80% or more and 99.9% or less, but is not limited thereto.

[0044] The above-described aerogel composite has a structure in which at least some of a plurality of aerogel particles are dispersed, preferably bonded, on the surface of a substrate containing fibers, and at the same time, at least some of a plurality of aerogel particles are dispersed, preferably located, in the empty spaces between the discrete fibers within the substrate. Examples of the substrate may be discrete fibers, films, sheets, nets, fibers, porous bodies, foams, nonwoven fabrics, or laminates of two or more layers thereof. Additionally, depending on the application, the surface may have a surface roughness or be patterned.

[0045] The above fiber substrate is polyester, polyolefin terephthalate, poly(ethylene) naphthalate, polycarbonate (e.g., rayon, nylon), cotton (e.g., Lycra® from DuPont), carbon (e.g., graphite), polyacrylonitrile (PAN), PAN oxide, non-carbonized heat-treated PAN (e.g., from SGL Carbon), glass fiber-based materials (S-glass, 901 glass, 902 glass, 475 glass, E-glass, etc.), silica-based fibers, e.g., quartz (e.g., Quartzel® from Saint-Gobain), Q-Fiber® felt (from Johns Manville), Saffil®, Durablanket® (from Uniflex), and other silica fibers, Duraback® (from carborundum), polyaramid fibers, e.g., Kevlar®, Nomex®, Sontera® (all from DuPont), CONEX (from Tyzine), polyolefin, e.g., Tyvek® (from DuPont), It may include Dyneema® (DSM), Spectra® (Honeywell), other polypropylene fibers such as Typar® and Xavan® (both DuPont), fluoropolymers such as PTFE under the brand name Teflon® (DuPont), Gore-tex® (WL GORE), silicon carbide fibers such as NICALCON (COI Ceramics), ceramic fibers such as NEXTEL (3M), acrylic polymers, wool, silk, hemp, leather, suede fibers, PBO fiber Xylon® (Tybo), liquid crystal materials such as VECTAN (Hoechst), Cambrel fibers (DuPont), polyurethane, polyamide, wool fibers, boron, aluminum, iron, stainless steel fibers, or other thermoplastic resins such as PEEK, PES, PET, PEK, and PPS, but any fiber that can further improve thermal insulation performance by including a space or void where the insertion of aerogel is easy may be used without limitation.

[0046] The thickness of the fiber substrate may be 0.5 to 20 mm, but is not limited thereto.

[0047] The above aerogel composite may have a fiber substrate and aerogel mixed from the top surface to the bottom surface, but is not limited thereto.

[0048] In addition, at least a portion of the upper or lower surface of the aerogel composite, preferably the entire surface, may have a flat shape. Here, the "flat shape" means that no irregularities are formed by intentional embossing or coating processes. Forming the upper and lower surfaces of the aerogel composite flat improves ease of operation when laminating support members, such as sheets, onto the upper and lower surfaces in the future, and increases the adhesion retention rate of the support members. Furthermore, it is desirable to reduce friction with adjacent equipment surfaces even when the aerogel composite itself is applied directly as an insulating material without support members.

[0049] The above aerogel composite has excellent elasticity, flexibility, and strength, so even when the aerogel composite is compressively deformed under a pressurized environment, it exhibits excellent elastic recovery and can maintain a high level of thermal insulation.

[0050] The density of the above aerogel composite is 0.05 to 0.50 g / cm³ 3 , 0.05 to 0.35 g / cm² 3 , 0.05 to 0.30 g / cm² 3 , 0.10 to 0.30 g / cm² 3 or 0.15 to 0.30 g / cm² 3 It may be, but is not limited to this.

[0051] When a pressure of 1 bar or more, 2 bar or more, 3 bar or more, 4 bar or more, 5 bar or more, 6 bar or more, 7 bar or more, 8 bar or more, 9 bar or more, 10 bar or more, 15 bar or more, 20 bar or more, 25 bar or more, 30 bar or more, 35 bar or more, or 40 bar or more, and, 50 bar or less, 45 bar or less, 40 bar or less, 35 bar or less, 30 bar or less, 25 bar or less, 20 bar or less, 15 bar or less, 10 bar or less, 9 bar or less, 8 bar or less, 7 bar or less, 6 bar or less, 5 bar or less, 4 bar or less, 3 bar or less, or 2 bar or less is applied in the horizontal direction (transverse direction) to the cross-section of the above aerogel composite, the compression recovery rate is 45% or more, 50% or more, 55% or more, 60% or more, 62% or more, 64% or more, It may be 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more.

[0052] The above "compression recovery rate" refers to the percentage of the cross-sectional thickness of the aerogel composite after a predetermined time has elapsed after compression relative to the cross-sectional thickness of the aerogel composite before compression, as shown in Formula 1 below. Here, the predetermined time may be, for example, 1 second or more, 5 seconds or more, 10 seconds or more, 30 seconds or more, 1 minute or more, 5 minutes or more, 10 minutes or more, 20 minutes or more, 30 minutes or more, 40 minutes or more, 50 minutes or more, 1 hour or more, 2 hours or more, 4 hours or more, 6 hours or more, 8 hours or more, 10 hours or more, 12 hours or more, 24 hours or more, 48 hours or more, or 96 hours or more, but is not limited thereto.

[0053] [Equation 1]

[0054] Compression recovery rate (%) = {(Cross-sectional thickness of aerogel composite after compression) / (Cross-sectional thickness of aerogel composite before compression)} X 100

[0055] The above "pressure" value refers to the actual pressure value applied per unit area of ​​the aerogel composite when applying pressure in the horizontal direction (transverse direction) to the cross-section of the aerogel composite using a press machine, etc. As an example, when applying pressure in the horizontal direction (transverse direction) to the cross-section of the aerogel composite using a press machine including a cylinder, the actual pressure value may refer to the value obtained by dividing the product of the cross-sectional area of ​​the cylinder and the set pressure value by the area of ​​the specimen, as shown in Equation 2 below, but is not limited thereto and may be calculated differently depending on the equipment or manufacturer.

[0056] [Equation 2]

[0057] Actual pressure value = (Inner diameter radius of press cylinder (cm) X Inner diameter radius of press cylinder (cm) X 3.14 X Set pressure value) / (Area of ​​specimen (cm²) 2 ))

[0058] In Equation 2 above, the unit of the inner radius of the cylinder can be, for example, cm, and the unit of the area of ​​the specimen can be, for example, cm 2 It may be, and the unit of the set pressure value may be bar or kgf, but is not limited thereto.

[0059] The time for applying pressure to the above-mentioned aerogel composite is not specifically limited, but, for example, it may be 1 second or more, 5 seconds or more, 10 seconds or more, 30 seconds or more, 1 minute or more, 5 minutes or more, 10 minutes or more, 20 minutes or more, 30 minutes or more, 40 minutes or more, 50 minutes or more, 1 hour or more, or 2 hours or more, and 24 hours or less, 12 hours or less, 10 hours or less, 8 hours or less, 6 hours or less, 4 hours or less, 2 hours or less, 1 hour or less, 50 minutes or less, 40 minutes or less, 30 minutes or less, 20 minutes or less, 10 minutes or less, 5 minutes or less, 1 minute or less, 30 seconds or less, 10 seconds or less, or 5 seconds or less, but is not limited thereto.

[0060] Applying pressure in the horizontal direction (transverse direction) to the cross-section of the above-mentioned aerogel composite means applying pressure to the aerogel composite in the direction from the upper surface to the lower surface or from the lower surface to the upper surface, that is, in the thickness direction.

[0061] As an example, when a pressure of 3 bar or more is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the compression recovery rate may be 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more.

[0062] As an example, when a pressure of 5 bar or more, 10 bar or more, 15 bar or more, 20 bar or more, 25 bar or more, 30 bar or more, or 35 bar or more is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the compression recovery rate may be 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more.

[0063] As an example, when a pressure of 3 bar is applied in the horizontal direction (transverse direction) to a cross-section of the aerogel composite, the compression recovery rate may be 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, preferably 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, more preferably 80% or more, 82% or more, 84% or more, 86% or more, It may be 88% or more, 90% or more, or 92% or more.

[0064] As an example, when a pressure of 9 bar is applied in the horizontal direction (transverse direction) to a cross-section of the aerogel composite, the compression recovery rate may be 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, and preferably 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more. It may be 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, and more preferably 70% or more, 72% or more, 74% or more, 76% or more, or 78% or more.

[0065] As an example, when a pressure of 15 bar is applied in the horizontal direction (transverse direction) to a cross-section of the aerogel composite, the compression recovery rate may be 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, and preferably 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% It may be 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, and more preferably 70% or more, 72% or more, 74% or more, or 76% or more.

[0066] As an example, when a pressure of 24 bar is applied in the horizontal direction (transverse direction) to a cross-section of the aerogel composite, the compression recovery rate may be 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, and preferably 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% It may be 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, and more preferably 70% or more, 72% or more, 74% or more, or 76% or more.

[0067] As an example, when a pressure of 30 bar is applied in the horizontal direction (transverse direction) to a cross-section of the aerogel composite, the compression recovery rate may be 53% or more, 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, and preferably 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% It may be 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, and more preferably 68% or more, 70% or more, 72% or more, 74% or more, or 76% or more.

[0068] As an example, when a pressure of 33 bar is applied in the horizontal direction (transverse direction) to a cross-section of the aerogel composite, the compression recovery rate may be 53% or more, 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, and preferably 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% It may be 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, and more preferably 68% or more, 70% or more, 72% or more, 74% or more, or 76% or more.

[0069] As an example, when a pressure of 37 bar is applied in the horizontal direction (transverse direction) to a cross-section of the aerogel composite, the compression recovery rate may be 50% or more, 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, 92% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, and preferably 55% or more, 60% or more, 62% or more, 64% or more, 66% or more, 68% or more, 70% or more, 72% or more, 74% or more, 76% It may be 78% or more, 80% or more, 82% or more, 84% or more, 86% or more, 88% or more, 90% or more, or 92% or more, and more preferably 55% or more, 60% or more, or 62% or more.

[0070] The thickness of the above aerogel composite before compression may be 20 mm or less, 15 mm or less, 14 mm or less, 13 mm or less, 12 mm or less, 11 mm or less, 10 mm or less, 9 mm or less, 8 mm or less, 7 mm or less, 6 mm or less, 5 mm or less, 4 mm or less, 3 mm or less, 2 mm or less, or 1 mm or less, and may have a thickness of 0.5 mm or more, 1 mm or more, or 2 mm or more, and can be appropriately adjusted by controlling the thickness of the substrate or the amount of aerogel sol impregnated into the substrate according to the application of the aerogel composite.

[0071] When a pressure of 1 bar or more, 2 bar or more, 3 bar or more, 4 bar or more, 5 bar or more, 6 bar or more, 7 bar or more, 8 bar or more, 9 bar or more, 10 bar or more, 15 bar or more, 20 bar or more, 25 bar or more, 30 bar or more, 35 bar or more, or 40 bar or more, and, 50 bar or less, 45 bar or less, 40 bar or less, 35 bar or less, 30 bar or less, 25 bar or less, 20 bar or less, 15 bar or less, 10 bar or less, 9 bar or less, 8 bar or less, 7 bar or less, 6 bar or less, 5 bar or less, 4 bar or less, 3 bar or less, or 2 bar or less is applied in the horizontal direction (transverse direction) to the cross-section of the above aerogel composite, the thermal transmittance after compression is 3 times or less, 2.9 times or less, 2.8 times or less, or 2.7 times or less compared to the thermal transmittance before compression. It may be 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less, and additionally may be 1 times or more or exceed 1 time.

[0072] The above "thermal transmittance" refers to the transfer of heat from one layer of air to another through a solid object, and 1 m per unit time 2Thermal conductivity refers to the amount of heat flowing when there is a 1°C temperature difference across a cross-sectional area, and it is the value obtained by dividing an object's thermal conductivity by its thickness. The amount of heat transferred by an object is influenced by its thermal conductivity and thickness; the higher the thermal conductivity and the thinner the thickness, the greater the amount of heat transferred. Therefore, for excellent thermal insulation performance, the thermal conductivity must be low and the thickness must be large. However, when pressure is applied to an elastic object, such as an aerogel composite, both the thermal conductivity and the thickness may change after pressurization. In other words, unless it is a perfectly elastic material, the thickness is bound to decrease after pressurization; if the thermal conductivity does not change, the total amount of heat transferred increases due to the reduction in thickness. Consequently, the thermal insulation performance is bound to deteriorate. Therefore, whether thermal insulation performance is maintained after pressurization cannot be verified solely by the post-pressurization thermal conductivity; it must be confirmed through the thermal transmittance, which considers both the post-pressurization thermal conductivity and the post-pressurization thickness. Even if thermal conductivity decreases or remains constant after pressurization, if the thickness decreases significantly after pressurization, the thermal transmittance and total heat transfer amount are bound to increase significantly.

[0073] The above aerogel composite does not change significantly in both thermal conductivity and thickness even after pressurization, so the rate of increase in thermal transmittance compared to before pressurization is not high, and the thermal insulation performance can be maintained at an excellent level without significant degradation due to pressurization.

[0074] The above "thermal transmittance after compression" refers to the ratio of thermal conductivity to the cross-sectional thickness of the aerogel composite after a predetermined time has elapsed following compression by applying a specific level of pressure in the horizontal direction (transverse direction) to the cross-section of the aerogel composite. Here, the predetermined time may be, for example, 1 second or more, 5 seconds or more, 10 seconds or more, 30 seconds or more, 1 minute or more, 5 minutes or more, 10 minutes or more, 20 minutes or more, 30 minutes or more, 40 minutes or more, 50 minutes or more, 60 minutes or more, 2 hours or more, 4 hours or more, 6 hours or more, 8 hours or more, 10 hours or more, 12 hours or more, 24 hours or more, 48 hours or more, or 96 hours or more, but is not limited thereto.

[0075] The time for applying pressure to the above-mentioned aerogel composite is not specifically limited, but, for example, it may be 1 second or more, 5 seconds or more, 10 seconds or more, 30 seconds or more, 1 minute or more, 5 minutes or more, 10 minutes or more, 20 minutes or more, 30 minutes or more, 40 minutes or more, 50 minutes or more, 1 hour or more, or 2 hours or more, and 24 hours or less, 12 hours or less, 10 hours or less, 8 hours or less, 6 hours or less, 4 hours or less, 2 hours or less, 1 hour or less, 50 minutes or less, 40 minutes or less, 30 minutes or less, 20 minutes or less, 10 minutes or less, 5 minutes or less, 1 minute or less, 30 seconds or less, 10 seconds or less, or 5 seconds or less, but is not limited thereto.

[0076] For example, when a pressure of 3 bar or more, 5 bar or more, 10 bar or more, 15 bar or more, 20 bar or more, 25 bar or more, 30 bar or more, or 35 bar or more is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the thermal transmittance after compression is 3 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, compared to the thermal transmittance before compression. It may be 1.02 times or less, or 1.01 times or less.

[0077] As an example, when pressure is applied to a cross-section of the aerogel composite in the horizontal direction (transverse direction) at a pressure value of 3 bar to 33 bar, the thermal transmittance after compression may be 2.0 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression.

[0078] As an example, when pressure is applied to a cross-section of the aerogel composite in the horizontal direction (transverse direction) at a pressure value of 3 bar to 24 bar, the thermal transmittance after compression may be 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression.

[0079] As an example, when pressure is applied to a cross-section of the aerogel composite in the horizontal direction (transverse direction) at a pressure value of 3 bar to 9 bar, the thermal transmittance after compression may be 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.45 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression.

[0080] As an example, when pressure is applied to a cross-section of the aerogel composite in the horizontal direction (transverse direction) at a pressure value of 9 bar to 33 bar, the thermal transmittance after compression may be 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression.

[0081] As an example, when pressure is applied to a cross-section of the aerogel composite in the horizontal direction (transverse direction) at a pressure value of 15 bar to 33 bar, the thermal transmittance after compression may be 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, or 1.05 times or less compared to the thermal transmittance before compression.

[0082] As an example, when pressure is applied to a cross-section of the aerogel composite in the horizontal direction (transverse direction) at a pressure value of 15 bar to 30 bar, the thermal transmittance after compression may be 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, or 1.05 times or less compared to the thermal transmittance before compression.

[0083] As an example, when pressure is applied to a cross-section of the aerogel composite in the horizontal direction (transverse direction) at a pressure value of 24 bar to 33 bar, the thermal transmittance after compression may be 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less compared to the thermal transmittance before compression.

[0084] As an example, when pressure is applied to a cross-section of the aerogel composite in the horizontal direction (transverse direction) at a pressure value of 24 bar to 30 bar, the thermal transmittance after compression may be 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less compared to the thermal transmittance before compression.

[0085] As an example, when pressure is applied to a cross-section of the aerogel composite in the horizontal direction (transverse direction) at a pressure value of 30 bar to 33 bar, the thermal transmittance after compression may be 3 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less compared to the thermal transmittance before compression.

[0086] As an example, when a pressure of 3 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the thermal transmittance after compression may be 1.45 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression, and preferably may be 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less.

[0087] For example, when a pressure of 3 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be 1.45 times or less compared to the heat transfer rate before compression. For example, when a pressure of 3 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be the same as the heat transfer rate before compression or 1.45 times or less compared to the heat transfer rate before compression. For example, when a pressure of 3 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be greater than the heat transfer rate before compression and 1.45 times or less compared to the heat transfer rate before compression.

[0088] As an example, when a pressure of 9 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the thermal transmittance after compression may be 1.85 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression, and preferably may be 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less.

[0089] For example, when a pressure of 9 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be 1.85 times or less compared to the heat transfer rate before compression. For example, when a pressure of 9 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be the same as the heat transfer rate before compression or 1.85 times or less compared to the heat transfer rate before compression. For example, when a pressure of 9 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be greater than the heat transfer rate before compression and 1.85 times or less compared to the heat transfer rate before compression.

[0090] As an example, when a pressure of 15 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the thermal transmittance after compression may be 2.35 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less compared to the thermal transmittance before compression, and preferably 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less. It may be 1.1 times or less or 1.05 times or less, and more preferably 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less.

[0091] For example, when a pressure of 15 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be 2.35 times or less compared to the heat transfer rate before compression. For example, when a pressure of 15 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be the same as the heat transfer rate before compression or 2.35 times or less compared to the heat transfer rate before compression. For example, when a pressure of 15 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be greater than the heat transfer rate before compression and 2.35 times or less compared to the heat transfer rate before compression.

[0092] As an example, when a pressure of 24 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the thermal transmittance after compression may be 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less, and preferably 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less. It may be 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, or 1.05 times or less, and more preferably 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less.

[0093] For example, when a pressure of 24 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be 2.7 times or less compared to the heat transfer rate before compression. For example, when a pressure of 24 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be the same as the heat transfer rate before compression or 2.7 times or less compared to the heat transfer rate before compression. For example, when a pressure of 24 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be greater than the heat transfer rate before compression and 2.7 times or less compared to the heat transfer rate before compression.

[0094] As an example, when a pressure of 30 bar is applied in the horizontal direction (transverse direction) to a cross-section of the aerogel composite, the thermal transmittance after compression may be 3 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less, and preferably 2.3 times or less, 2.2 times or less, 2.1 times or less. It may be 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, or 1.05 times or less, and more preferably 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less.

[0095] For example, when a pressure of 30 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be 3 times or less than the heat transfer rate before compression. For example, when a pressure of 30 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be the same as the heat transfer rate before compression or 3 times or less than the heat transfer rate before compression. For example, when a pressure of 30 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be greater than the heat transfer rate before compression and 3 times or less than the heat transfer rate before compression.

[0096] As an example, when a pressure of 33 bar is applied in the horizontal direction (transverse direction) to a cross-section of the aerogel composite, the thermal transmittance after compression may be 3 times or less, 2.9 times or less, 2.8 times or less, 2.7 times or less, 2.6 times or less, 2.5 times or less, 2.4 times or less, 2.3 times or less, 2.2 times or less, 2.1 times or less, 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, 1.1 times or less, 1.05 times or less, 1.04 times or less, 1.03 times or less, 1.02 times or less, or 1.01 times or less, and preferably 2.3 times or less, 2.2 times or less, 2.1 times or less. It may be 2 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, 1.2 times or less, or 1.1 times or less, and more preferably 2.0 times or less, 1.9 times or less, 1.8 times or less, 1.7 times or less, 1.6 times or less, 1.5 times or less, 1.4 times or less, 1.3 times or less, or 1.2 times or less.

[0097] For example, when a pressure of 33 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be 3 times or less than the heat transfer rate before compression. For example, when a pressure of 33 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be the same as the heat transfer rate before compression or 3 times or less than the heat transfer rate before compression. For example, when a pressure of 33 bar is applied in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, the heat transfer rate after compression may be greater than the heat transfer rate before compression and 3 times or less than the heat transfer rate before compression.

[0098] When the above aerogel composite is compressed by applying at least one of 3 bar, 9 bar, and 24 bar in the transverse direction, the thermal transmittance after compression may be the same as or 1.8 times or less than the thermal transmittance before compression.

[0099] When the above aerogel composite is compressed by applying pressures of 3 bar, 9 bar, and 24 bar in the transverse direction, respectively, the thermal transmittance after compression may be the same as or 1.8 times or less than the thermal transmittance before compression.

[0100] When the above aerogel composite is compressed by applying pressures of 3 bar, 9 bar, and 24 bar in the transverse direction, respectively, the thermal transmittance after compression may be greater than or less than 1.8 times the thermal transmittance before compression.

[0101] As described above, when measuring the recovery rate or thermal transmittance after compression using a press machine, etc., a single specimen can be prepared from the aerogel composite for measurement. However, depending on the measuring equipment, if the width or length of the aerogel composite is smaller than the part where the pressure of the measuring equipment is applied, the aerogel composite is cut into two or more pieces, and then rearranged so that both the width and length are larger than the pressure-applying equipment. Even if the compression recovery rate or thermal transmittance is measured, the measured value is considered to be substantially the same as that of a single specimen.

[0102] As an example, the recovery rate after compression or the thermal transmittance after compression may be measured for a rectangular aerogel composite specimen having dimensions of 20 cm x 20 cm. In this case, if the width or length of the fabricated aerogel composite is smaller than 20 cm, two or more specimens may be arranged in parallel adjacent to each other to make the specimen size 20 cm x 20 cm, and then measurements may be performed on such specimens.

[0103] The above-mentioned aerogel composite can maintain an excellent level of thermal insulation performance without significant degradation, as the thermal transmittance before and after compression is maintained within a specific range regardless of the intensity of the pressure applied (or compressed).

[0104] Specifically, the heat transfer coefficient obtained after compression of the aerogel composite to at least one pressure value among 0 to 24 bar may satisfy the following Equation 3:

[0105] [Equation 3]

[0106] {(Thermal transmittance before and after compression (a)) - (Average value of thermal transmittances before and after compression (b))} = (Average value of thermal transmittances before and after compression (b)) XA

[0107] In the above Equation 3, "thermal transmittance before and after compression (a)" refers to the thermal transmittance obtained after compression with respect to the cross-section of the aerogel composite in the horizontal direction (transverse direction) at least one pressure value in the range of 0 to 24 bar. As an example, the thermal transmittance before and after compression (a) may refer to the thermal transmittance obtained after compression by applying a pressure of 0 bar, 3 bar, 9 bar, or 24 bar to the aerogel composite. Here, the pressure of 0 bar refers to no pressure applied (uncompressed), and accordingly, the thermal transmittance obtained after compression by applying a pressure of 0 bar refers to the thermal transmittance of the aerogel composite without pressure applied.

[0108] In addition, the "average value of thermal transmittances before and after compression (b)" refers to the thermal transmittance of the aerogel composite without applying pressure (or compression) and the average value of the thermal transmittances obtained after compression with at least two pressure values ​​in the range of greater than 0 bar and less than or equal to 24 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite. As an example, it may refer to the average value of the thermal transmittances obtained after compression by applying pressure to at least two pressure values ​​among 0 bar, 3 bar, 9 bar, and 24 bar to the aerogel composite.

[0109] The above A may be a rational number of -0.30 to +0.30, a rational number of -0.25 to +0.25, a rational number of -0.24 to +0.24, a rational number of -0.23 to +0.23, a rational number of -0.22 to +0.22, a rational number of -0.21 to +0.21, a rational number of -0.20 to +0.20, a rational number of -0.19 to +0.19, a rational number of -0.15 to +0.15, a rational number of -0.14 to +0.14, a rational number of -0.13 to +0.13, a rational number of -0.12 to +0.12, a rational number of -0.11 to +0.11, or a rational number of -0.10 to +0.10.

[0110] As an example, the thermal transmittance of an uncompressed (0 bar compression) aerogel composite that is not pressurized may satisfy Equation 3 above. In this case, the average value (b) of the thermal transmittances before and after compression may mean the thermal transmittance of the uncompressed aerogel composite and the average value of the thermal transmittances obtained after compression to at least two pressure values ​​among 3 bar, 9 bar, and 24 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite.

[0111] As an example, the thermal transmittance obtained after compressing an aerogel composite with a pressure of 3 bar, 9 bar, or 24 bar may satisfy Equation 3 above. In this case, the average value (b) of the thermal transmittances before and after compression may mean the thermal transmittance of the uncompressed (0 bar compression) aerogel composite and the average value of the thermal transmittances obtained after compressing at least two pressure values ​​among 3 bar, 9 bar, and 24 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite.

[0112] As an example, the average value (b) of the thermal transmittances before and after compression refers to the thermal transmittance of an uncompressed (0 bar compression) aerogel composite and the average value of the thermal transmittances obtained after compression by applying pressures of 3 bar, 9 bar, and 24 bar, respectively, in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, and in this case, A may be a rational number of -0.30 to +0.30, a rational number of -0.25 to +0.25, a rational number of -0.24 to +0.24, a rational number of -0.23 to +0.23, or -0.22 to +0.22.

[0113] As an example, the average value (b) of the thermal transmittances before and after compression refers to the thermal transmittance of the uncompressed (0 bar compression) aerogel composite and the average value of the thermal transmittances obtained after compression by applying pressures of 3 bar and 9 bar, respectively, in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, and in this case, A may be a rational number of -0.25 to +0.25, a rational number of -0.24 to +0.24, a rational number of -0.23 to +0.23, a rational number of -0.22 to +0.22, a rational number of -0.21 to +0.21, or a rational number of -0.20 to +0.20.

[0114] The thermal transmittance obtained after compressing the aerogel composite with a pressure of 0 bar, 3 bar, 9 bar, or 24 bar may satisfy Equation 3 above. Here, the average value (b) of the thermal transmittances before and after compression refers to the thermal transmittance of the uncompressed (0 bar compression) aerogel composite and the average value of the thermal transmittances obtained after compressing the cross-section of the aerogel composite with at least two pressure values ​​among 3 bar, 9 bar, and 24 bar in the horizontal direction (transverse direction). In this case, A may be a rational number ranging from -0.25 to +0.25.

[0115] In addition, the above-mentioned aerogel composite can maintain an excellent level of thermal insulation performance without significant degradation, as the thermal transmittance after compression is maintained within a specific range even when pressurized (or compressed) by any intensity of pressure.

[0116] Specifically, the heat transfer coefficient obtained after compression of the aerogel composite to at least one pressure value between 3 and 30 bar can satisfy the following Equation 4:

[0117] [Equation 4]

[0118] (Thermal transmittance after compression (c) - Average value of thermal transmittances after compression (d)) = (Average value of thermal transmittances after compression (d)) XB

[0119] In the above Equation 4, "thermal transmittance after compression (c)" refers to the thermal transmittance obtained after compression with at least one pressure value in the range of 3 to 30 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite. As an example, the thermal transmittance after compression (c) may refer to the thermal transmittance obtained after compression by applying a pressure of 3 bar, 9 bar, 15 bar, 24 bar, or 30 bar; as another example, it may refer to the thermal transmittance obtained after compression by applying a pressure of 3 bar, 9 bar, or 24 bar; and as yet another example, it may refer to the thermal transmittance obtained after compression by applying a pressure of 9 bar, 15 bar, 24 bar, or 30 bar.

[0120] In addition, the "average value of thermal transmittances after compression (d)" refers to the average value of thermal transmittances obtained after compression with at least two pressure values ​​in the range of 3 to 30 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite. As an example, the average value of thermal transmittances after compression (d) may refer to the average value of thermal transmittances obtained after compression by applying pressures of 3 bar, 9 bar, and 24 bar, respectively, and as another example, may refer to the average value of thermal transmittances obtained after compression by applying pressures of 9 bar, 15 bar, 24 bar, and 30 bar, respectively.

[0121] The above B may be a rational number of -0.25 to +0.25, a rational number of -0.24 to +0.24, a rational number of -0.23 to +0.23, a rational number of -0.22 to +0.22, a rational number of -0.21 to +0.21, a rational number of -0.20 to +0.20, a rational number of -0.19 to +0.19, a rational number of -0.15 to +0.15, a rational number of -0.14 to +0.14, a rational number of -0.13 to +0.13, a rational number of -0.12 to +0.12, a rational number of -0.11 to +0.11, or a rational number of -0.10 to +0.10.

[0122] As an example, the thermal transmittance obtained after compressing the aerogel composite with a pressure of 9 bar, 15 bar, 24 bar, or 30 bar may satisfy Equation 4. In this case, in Equation 4, the thermal transmittance after compression (c) refers to the thermal transmittance obtained after compressing the cross-section of the aerogel composite with a pressure value of 9 bar, 15 bar, 24 bar, or 30 bar in the horizontal direction (transverse direction), and the average value of the thermal transmittances after compression (d) may refer to the average value of the thermal transmittances obtained after compressing the cross-section of the aerogel composite with at least two pressure values ​​among 9 bar, 15 bar, 24 bar, and 30 bar in the horizontal direction (transverse direction).

[0123] As an example, the heat transfer rate obtained after compressing the above aerogel composite at pressures of 9 bar, 15 bar, 24 bar, and 30 bar, respectively, can satisfy Equation 4 above. In this case, in Equation 4 above, the thermal transmittance after compression (c) refers to the thermal transmittance obtained after compression with any one of the pressure values ​​of 9 bar, 15 bar, 24 bar, and 30 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite, and the average value of the thermal transmittances after compression (d) refers to the average value of the thermal transmittances obtained after compression with each of the pressure values ​​of 9 bar, 15 bar, 24 bar, and 30 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite, and B may be a rational number of -0.15 to +0.15, a rational number of -0.14 to +0.14, a rational number of -0.13 to +0.13, a rational number of -0.12 to +0.12, a rational number of -0.11 to +0.11, or a rational number of -0.10 to +0.10.

[0124] As an example, the thermal transmittance obtained after compressing the aerogel composite with a pressure of 3 bar, 9 bar, or 24 bar may satisfy Equation 4. In this case, in Equation 4, the thermal transmittance after compression (c) refers to the thermal transmittance obtained after compressing the cross-section of the aerogel composite with a pressure value of 3 bar, 9 bar, or 24 bar in the horizontal direction (transverse direction), and the average value of the thermal transmittances after compression (d) may refer to the average value of the thermal transmittances obtained after compressing the cross-section of the aerogel composite with at least two pressure values ​​among 3 bar, 9 bar, and 24 bar in the horizontal direction (transverse direction).

[0125] As an example, the heat transfer rate obtained after compressing the above aerogel composite with pressures of 3 bar, 9 bar, and 24 bar can satisfy Equation 4 above. In this case, in Equation 4 above, the thermal transmittance after compression (c) refers to the thermal transmittance obtained after compression with any one of 3 bar, 9 bar, and 24 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite, and the average value of the thermal transmittances after compression (d) refers to the average value of the thermal transmittances obtained after compression with each of 3 bar, 9 bar, and 24 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite, and B may be a rational number from -0.25 to +0.25, a rational number from -0.24 to +0.24, a rational number from -0.23 to +0.23, a rational number from -0.22 to +0.22, a rational number from -0.21 to +0.2, a rational number from -0.20 to +0.20, or a rational number from -0.19 to +0.19.

[0126] In addition, for the aerogel composite, the rate of change (C) of the thermal transmittance after compression per unit applied pressure, represented by the following Equation 5, may be a rational number of -0.10 or more, -0.09 or more, -0.08 or more, -0.07 or more, -0.06 or more, -0.05 or more, -0.04 or more, -0.03 or more, -0.02 or more, or -0.01 or more, and may be a rational number of +0.10 or less, +0.09 or less, +0.08 or less, +0.07 or less, +0.06 or less, +0.05 or less, +0.04 or less, +0.03 or less, +0.02 or less, or +0.01 or less. Preferably, it may be a rational number of -0.10 to +0.10, a rational number of -0.09 to +0.09, a rational number of -0.08 to +0.08, a rational number of -0.07 to +0.07, a rational number of -0.06 to +0.06, or a rational number of -0.05 to +0.05:

[0127] [Equation 5]

[0128] C = (Thermal transmittance after compression at pressure x - Thermal transmittance after compression at pressure y) / (x - y)

[0129] In the above Equation 5, x and y are each independently different pressure values ​​(in units of bar) within the pressure range of 3 to 24 bar.

[0130] As an example, in the above Equation 5, x and y can each independently be any one of the pressure values ​​of 3 bar, 9 bar, 15 bar and 24 bar.

[0131] As an example, in the above Equation 5, x can be 24 bar and y can be 3 bar.

[0132] For example, in the above Equation 5, x can be 24 bar and y can be 9 bar.

[0133] For example, in the above Equation 5, x can be 15 bar and y can be 9 bar.

[0134] As an example, in the above Equation 5, x can be 24 bar and y can be 15 bar.

[0135] As an example, the rate of change (C) of the thermal transmittance after compression per unit applied pressure may be a rational number ranging from -0.10 to +0.10.

[0136] In addition, the above aerogel composite may satisfy Formula 6 below:

[0137] [Equation 6]

[0138] Thermal transmittance after compression (e) = Average value of thermal transmittances after compression (f) XD

[0139] In the above Equation 6, "thermal transmittance after compression (e)" refers to the thermal transmittance obtained after compression by applying a pressure of 3 bar, 9 bar, 15 bar, 24 bar, or 30 bar in the horizontal direction (transverse direction) to the cross-section of the aerogel composite, and

[0140] The above "average value of thermal transmittances after compression (f)" refers to the average value of thermal transmittances obtained after compression with respect to the cross-section of the aerogel composite in the horizontal direction (transverse direction) at least two pressure values ​​among 3 bar, 9 bar, 15 bar, 24 bar, and 30 bar, and

[0141] The above D is a rational number from 0.70 to 1.20, a rational number from 0.75 to 1.20, a rational number from 0.80 to 1.20, a rational number from 0.85 to 1.20, a rational number from 0.75 to 1.18, a rational number from 0.80 to 1.18, a rational number from 0.85 to 1.18, a rational number from 0.75 to 1.16, a rational number from 0.80 to 1.16, a rational number from 0.85 to 1.16, a rational number from 0.80 to 1.14, a rational number from 0.85 to 1.14, a rational number from 0.80 to 1.12, a rational number from 0.85 to 1.12, a rational number from 0.85 to 1.10, a rational number from 0.90 to 1.12, or It can be a rational number between 0.85 and 1.10.

[0142] As an example, in the above Equation 6, the thermal transmittance (e) after compression is the thermal transmittance obtained after compression with a pressure of 9 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite, and the average value (f) of the thermal transmittances after compression is the average value of the thermal transmittances obtained after compression by applying pressures of 9 bar, 15 bar, 24 bar, and 30 bar, respectively, and in this case, D may be a rational number of 0.85 to 1.12, a rational number of 0.90 to 1.12, a rational number of 0.85 to 1.10, a rational number of 0.90 to 1.10, a rational number of 0.85 to 1.0, or a rational number of 0.90 to 1.0.

[0143] As an example, in the above Equation 6, the thermal transmittance (e) after compression is the thermal transmittance obtained after compression with a pressure of 30 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite, and the average value (f) of the thermal transmittances after compression is the average value of the thermal transmittances obtained after compression by applying pressures of 9 bar, 15 bar, 24 bar, and 30 bar, respectively, and in this case, D may be a rational number of 0.90 to 1.12, a rational number of 0.95 to 1.12, a rational number of 0.90 to 1.10, a rational number of 0.95 to 1.10, a rational number of 1.0 to 1.12, or a rational number of 1.0 to 1.10.

[0144] As an example, in Equation 6 above, the thermal transmittance after compression (e) is the thermal transmittance obtained after compression with a pressure of 3 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite, and the average value of the thermal transmittances after compression (f) is the average value of the thermal transmittances obtained after compression by applying pressures of 3 bar, 9 bar, and 24 bar, respectively, wherein D is a rational number from 0.75 to 1.20, a rational number from 0.75 to 1.18, a rational number from 0.75 to 1.16, a rational number from 0.75 to 1.14, a rational number from 0.80 to 1.14, a rational number from 0.75 to 1.20, a rational number from 0.80 to 1.12, a rational number from 0.75 to 1.10, a rational number from 0.80 to 1.10, a rational number from 0.75 to 1.05, or It can be a rational number between 0.80 and 1.05.

[0145] As an example, in the above Equation 6, the thermal transmittance (e) after compression is the thermal transmittance obtained after compression with a pressure of 24 bar in the horizontal direction (transverse direction) with respect to the cross-section of the aerogel composite, and the average value (f) of the thermal transmittances after compression is the average value of the thermal transmittances obtained after compression by applying pressures of 3 bar, 9 bar, and 24 bar, respectively, and in this case, D may be a rational number of 0.80 to 1.20, a rational number of 0.85 to 1.20, a rational number of 0.85 to 1.18, a rational number of 0.90 to 1.18, a rational number of 0.85 to 1.16, a rational number of 0.90 to 1.16, a rational number of 0.95 to 1.16, or a rational number of 1.0 to 1.16.

[0146] The above aerogel composite may have excellent mechanical strength, with a compressive strength at 10% strain of 20 kPa to 80 kPa, 20 kPa to 70 kPa, 30 kPa to 80 kPa, 30 kPa to 70 kPa, 35 kPa to 80 kPa, or 35 kPa to 70 kPa. Here, the compressive strength may be measured by preparing a specimen according to ASTM C165.

[0147] The above aerogel composite has a tensile strength of 30 N / cm 2 up to 60 N / cm 2 , 40 N / cm 2 Up to 55 N / cm 2 , or 45 N / cm 2 Up to 55 N / cm 2 As such, it may have excellent flexibility. Here, the tensile strength may be measured by manufacturing a specimen according to ASTM D638 standards.

[0148] In the present invention, the aerogel composite may generally be formed by a step of preparing a silica sol; a step of gelling after impregnating a fiber substrate with the silica sol; and a drying step. Each step is described below. However, the specific manufacturing processes or examples described herein are not intended to limit any specific type of aerogel or its manufacturing method. This specification may include any aerogel formed by any associated manufacturing method known to a person skilled in the art.

[0149] Preparation steps for silica sol;

[0150] In the present invention, a silica sol can be prepared by mixing a silica precursor composition and a catalyst composition.

[0151] The above silica precursor composition may include water and / or a polar organic solvent in the silica precursor.

[0152] The above silica precursor can be any precursor that can be used to form a silica aerogel without limitation, and may be, for example, a silicon-containing alkoxide-based compound. Specifically, tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetrasecondary butyl orthosilicate, tetra tertiary butyl orthosilicate, tetrahexyl orthosilicate, and tetracyclohexyl orthosilicate. It may be a tetraalkyl silicate such as tetradodecyl orthosilicate, tetradodecyl orthosilicate, etc. More specifically among these, the silica precursor may be tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), or a mixture thereof.

[0153] In addition, the silica precursor may be a water glass solution. Here, the water glass solution may refer to a diluted solution obtained by adding distilled water to water glass and mixing it, and the water glass may be sodium silicate (Na2SiO3), which is an alkali silicate obtained by melting silicon dioxide (SiO2) and an alkali.

[0154] In addition, the silica precursor may include pre-hydrolyzed TEOS (HTEOS). HTEOS is an ethyl silicate oligomer material with a broad molecular weight distribution, and since it can control physical properties such as gelation time when synthesized from TEOS monomers in the form of an oligomer, it can be easily applied according to the user's reaction conditions. Furthermore, it has the advantage of producing reproducible physical properties of the final product. The HTEOS may generally be synthesized by a condensation reaction of TEOS that has undergone a partial hydration step under acidic conditions. That is, the HTEOS may be in the form of an oligomer prepared by condensing TEOS, and the oligomer may be partially hydrated.

[0155] The above silica precursor composition may further include a silicate containing a hydrophobic group. The silicate containing the hydrophobic group is not limited in type as long as it is an alkyl silane compound containing a silane functional group capable of reacting with an alkyl group that induces hydrophobization and a -Si-O- functional group of the wet gel, but specific examples include one or more selected from the group consisting of methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), trimethylsilanol (TMS), methyltrimethoxysilane (MTMS), dimethyldiethoxysilane (DMDEOS), ethyltriethoxysilane (ETES), and phenyltriethoxysilane (PTES), but is not limited thereto.

[0156] When the silica precursor composition contains the silicate containing the hydrophobic group, it may be included in a molar ratio of 2:98 to 98:2 (molar ratio of silicate containing the hydrophobic group to tetraalkyl silicate) with the tetraalkyl silicate. Within this range, the strength and thermal insulation performance of the aerogel can be secured with high efficiency, while preventing shrinkage during atmospheric pressure drying, thereby preventing a decrease in thermal insulation performance.

[0157] The silica concentration of the above silica precursor composition is 10 kg / m³ 3 up to 100 kg / m² 3 , 20 kg / m 3 up to 80 kg / m² 3 , 30 kg / m 3 Up to 70 kg / m² 3 , 30 kg / m 3 up to 60 kg / m² 3 , or 35 kg / m² 3 Up to 45 kg / m 3 It may be, but is not limited thereto. The above silica concentration is the concentration of silica contained in the silica precursor relative to the silica precursor composition, and can be appropriately adjusted by varying the content of the silica precursor, organic solvent, and water.

[0158] The above silica precursor may be used in an amount such that the silica content contained in the silica sol is 0.1% by weight to 30% by weight, but is not limited thereto. If the silica content satisfies the above range, it is desirable in terms of securing excellent mechanical properties, particularly flexibility, of the aerogel composite while also having an improved thermal insulation effect.

[0159] The above polar organic solvent may include alcohols, specifically examples of which include monohydric alcohols such as methanol, ethanol, isopropanol, butanol, etc.; polyhydric alcohols such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and sorbitol, etc.; or combinations thereof, but other solvents known to those skilled in the art may also be used without limitation. Among these, the polar organic solvent may be a monohydric alcohol having 1 to 6 carbon atoms, such as methanol, ethanol, isopropanol, butanol, etc., such as ethanol, when considering miscibility with water and aerogel.

[0160] The above polar organic solvent can be used in an appropriate amount by a person skilled in the art, taking into account the degree of hydrophobicity in the final aerogel composite while promoting the surface modification reaction.

[0161] When preparing the above silica precursor composition, if a fully hydrolyzed silica precursor is prepared, the silica precursor and an organic solvent may be mixed in a weight ratio of 1:0.1 to 1.5, 1:0.5 to 1.5, or 1:0.5 to 1.2, but are not limited thereto.

[0162] When preparing the above silica precursor composition, if a fully hydrolyzed silica precursor is prepared, the silica precursor and water may be mixed in a molar ratio of 1:0.1 to 10, 1:1 to 8, or 1:2 to 6, but are not limited thereto.

[0163] In addition, when preparing the above silica precursor composition, if the silica precursor contains TEOS that has been fully hydrolyzed, the composition may be prepared by mixing the fully hydrolyzed TEOS and an organic solvent in a weight ratio of 1:2 to 10, 1:3 to 8, or 1:3 to 6, but is not limited thereto.

[0164] The above silica precursor composition may further include an acid catalyst, specifically, when an alkoxysilane compound other than a hydrolysate is used as a precursor, the acid catalyst may further include an acid catalyst. In this case, any acid catalyst that lowers the pH to 3 or lower can be used without limitation, and examples include hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, oxalic acid, or acetic acid. In this case, the acid catalyst may be added in an amount that lowers the pH of the sol to 3 or lower, or it may be added in the form of an aqueous solution dissolved in an aqueous solvent.

[0165] The above catalyst composition may include an inorganic base such as sodium hydroxide or potassium hydroxide as a base catalyst; or an organic base such as ammonium hydroxide. Specific examples include sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia (NH3), ammonium hydroxide (NH4OH; ammonia solution), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol, 2-(methylamino)ethanol, N-methyl diethanolamine, dimethylaminoethanol, diethylaminoethanol, nitrilotriethanol, It may be 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine, dibutanolamine, pyridine, or a combination thereof, but is not limited thereto.

[0166] The above base catalyst may be included in an amount such that the pH of the sol becomes 5 to 9. If the pH of the sol falls outside this range, gelation may not be easy or the gelation rate may become excessively slow, potentially leading to reduced processability. Additionally, since the base may precipitate when added in a solid state, it may be preferable to add it in a solution diluted by an aqueous solvent or the aforementioned organic solvent. In this case, the dilution ratio of the base catalyst and the organic solvent, specifically the alcohol, may be 1:4 to 1:100 by volume, but is not limited thereto.

[0167] The above catalyst composition further includes an alkoxysilane compound having a hydrophobic group, so that the hydrophobic agent reacts with the silica wet gel to strengthen the structure and surface modification can be achieved.

[0168] The alkoxysilane compound having the above-mentioned hydrophobic group is not limited to any specific type as long as it is an alkyl silane compound containing a silane functional group capable of reacting with an alkyl group that induces hydrophobization and a -Si-O- functional group of the wet gel, but specific examples include one or more selected from the group consisting of trimethylethoxysilane (TMES), trimethylsilanol (TMS), trimethylchlorosilane (TMCS), methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), dimethyldiethoxysilane (DMDEOS), ethyltriethoxysilane, and phenyltriethoxysilane, but is not limited thereto.

[0169] The alkoxysilane compound having the above-mentioned hydrophobic group may be included in an amount of 3 to 15 parts by weight, 5 to 10 parts by weight, or 6 to 8 parts by weight based on 100 parts by weight of silica sol, but is not limited thereto.

[0170] However, if the catalyst composition includes an alkoxysilane compound having a hydrophob, it may include water to promote the surface modification reaction. The catalyst composition may include 3 to 8 equivalents, 4 to 8 equivalents, or 5 to 6 equivalents of water based on 1 equivalent of the hydrophobizing agent.

[0171] To prepare the silica sol, the silica precursor composition and the catalyst composition may be mixed in a volume ratio of 1:0.01 to 10.0, 1:0.01 to 5.0, or 1:0.01 to 2.0, but are not limited thereto.

[0172] If necessary, additional additives may be added to the silica sol. In this case, any known additives that can be added when manufacturing an aerogel may be used, and for example, additives such as opacifiers and flame retardants may be used.

[0173] The above additive may be added in an amount of 0.1% to 10% by weight, 0.1% to 7% by weight, 0.5% to 7% by weight, or 0.5% to 5% by weight with respect to the silica content of the aerogel, but is not limited thereto.

[0174] Gelation step of silica sol

[0175] In the present invention, silica sol can be impregnated into a substrate and then gelled.

[0176] The above impregnation process is a process that allows the catalytic silica sol to penetrate into the internal pores of the substrate. It can be performed by introducing the catalytic silica sol and the substrate into a reaction vessel, or by spraying the catalytic silica sol onto the substrate moving on a conveyor belt according to a roll-to-roll process. At this time, to improve the bonding between the substrate and the silica sol, the substrate can be lightly pressed to ensure sufficient impregnation. Subsequently, the material can be pressed to a certain thickness under a constant pressure to remove excess silica sol, thereby reducing the drying time.

[0177] The temperature of the silica sol in the reaction vessel may be 1 to 40 ℃, 20 to 40 ℃, 25 to 40 ℃, 30 to 40 ℃, or 35 to 45 ℃. It is preferable that the temperature of the silica sol in the reaction vessel satisfies the above ranges, as this allows for the more easily achieving an appropriate viscosity range of the catalyzed sol and enables the satisfaction of the desired viscosity range even with a relatively short residence time.

[0178] The above-mentioned catalyzed silica sol can be impregnated into a substrate in a volume ratio of 0.1 to 10:1 (catalyzed silica sol:substrate), 0.1 to 1:1, 0.3 to 1:1, 0.5 to 1:1, or 0.7 to 1:1, but is not limited thereto.

[0179] In the present invention, the silica sol impregnated in the substrate can be gelled simultaneously with the impregnation process of the silica sol or sequentially after the impregnation process.

[0180] The substrate impregnated with the above-mentioned catalystd sol can be gelled on a moving element such as a conveyor belt.

[0181] The above "gelation" may refer to a sol-gel reaction, and the above "sol-gel reaction" may refer to forming a network structure from a silicon unit precursor material. Here, the network structure may refer to a planar net-like structure in which a specific polygon with one or more types of atomic arrangements is connected, or a structure that forms a three-dimensional skeletal structure by sharing vertices, edges, faces, etc. of a specific polyhedron.

[0182] The above gelation may be performed under an atmosphere temperature of 20 to 40 ℃, 20 to 30 ℃, 25 to 40 ℃, 30 to 40 ℃, or 35 to 40 ℃, and the gelation time may be performed for 1 to 120 minutes, 1 to 100 minutes, 1 to 60 minutes, 5 to 60 minutes, 5 to 40 minutes, 10 to 40 minutes, 10 to 30 minutes, or 10 to 20 minutes, but is not limited thereto.

[0183] Aging stage of the gelled wet gel complex

[0184] If necessary, an aging step may be further included to allow the wet gel composite obtained by gelation as described above to be left at an appropriate temperature to allow the chemical change to be fully completed. In the aging step, the network structure formed by gelation can be formed more firmly, thereby improving the mechanical stability of the aerogel composite.

[0185] The above aging step can be performed by leaving the gelled wet gel complex as is at an appropriate temperature, or by adding a cross-linking promoting compound.

[0186] In addition, during the aging step, the process may be carried out in the presence of the wet gel complex by adding a solution of a base catalyst, such as sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonium hydroxide (NH4OH), triethylamine, or pyridine, diluted in an organic solvent to a concentration of 1 to 10%. In this case, Si-O-Si bonds within the aerogel are induced to the maximum extent, making the network structure of the silica gel more robust and facilitating the maintenance of the pore structure during the subsequent drying process. At this time, the organic solvent may be the aforementioned alcohol, and specifically, may include ethanol.

[0187] The above aging step can be carried out by leaving the product at a temperature of 30°C to 80°C, 40°C to 80°C, or 50°C to 80°C for 0.1 to 20 hours, 0.5 to 15 hours, 0.5 to 10 hours, 0.5 to 7 hours, or 1 to 5 hours to strengthen the pore structure, and within this range, it is possible to prevent a decrease in productivity while preventing the loss of solvent due to evaporation, thereby preventing an increase in production costs.

[0188] In addition, the above aging step may be performed by first aging at 30°C to 80°C for 0.1 to 5 hours to strengthen the pore structure, and then second aging may be performed at 30°C to 80°C for 0.1 to 20 hours, 0.5 to 15 hours, 0.5 to 10 hours, 0.5 to 7 hours, or 1 to 5 hours in the presence of a solution in which a base catalyst is diluted in an organic solvent to a concentration of 1 to 10%.

[0189] In addition, during the aging step (or during the second aging step if performed in two stages), a mixed solution of an alkoxysilane compound and an alcohol can be added to provide not only unreacted sol but also an additional sol precursor source, thereby inducing additional gelation in the silica gel network structure and further strengthening the gel structure. At this time, the alkoxysilane compound may be included in an amount of 0.5 to 9.5 parts by weight, 1.0 to 9.5 parts by weight, or 1.5 to 9.5 parts by weight relative to 100 parts by weight of the total aging solution.

[0190] The above alkoxysilane compounds are tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetrasecondary butyl orthosilicate, tetratertiary butyl orthosilicate, tetrahexyl orthosilicate, and tetracyclohexyl It may include one or more selected from the group consisting of tetracyclohexyl orthosilicate, tetradodecyl orthosilicate, methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), trimethylsilanol (TMS), trimethylchlorosilane (TMCS), ethyltriethoxysilane (ETES), dimethyldiethoxysilane (DMDEOS), and phenyltriethoxysilane.

[0191] In addition, the above alcohol may specifically be a monohydric alcohol such as methanol, ethanol, isopropanol, butanol, etc.; or a polyhydric alcohol such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and sorbitol, etc., and preferably may be a monohydric alcohol having 1 to 6 carbon atoms such as methanol, ethanol, isopropanol, butanol, etc., e.g. ethanol, but is not limited thereto.

[0192] The above aging step may be performed in a separate reaction vessel after recovering the gelled wet gel complex, or it may be performed inside the reaction vessel where the gelling step was performed.

[0193] Surface modification step of aged wet gel complex

[0194] If necessary, a surface modification step may be further included to hydrophobize the surface of the wet gel complex obtained by gelation as described above or the aged wet gel complex in the presence of a surface modifier.

[0195] The above surface modifier may be any compound that hydrophobicizes the wet gel surface without limitation, such as a silane compound, a siloxane compound, a silanol compound, a silazane compound, or a combination thereof. Specific examples include silane compounds comprising trimethylchlorosilane (TMCS), dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), vinyltrimethoxysilane, ethyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, tetraethoxysilane, dimethyldichlorosilane, 3-aminopropyltriethoxysilane, etc.; and siloxane compounds comprising polydimethylsiloxane, polydiethylsiloxane, or octamethylcyclotetrasiloxane, etc. Silanol-based compounds including trimethylsilanol, triethylsilanol, triphenylsilanol, and t-butyldimethylsilanol, etc.; silazane-based compounds including 1,2-diethyldisilazane, 1,1,2,2-tetramethyldisilazane, 1,1,3,3-tetramethyldisilazane, 1,1,1,2,2,2-hexamethyldisilazane (HMDS), 1,1,2,2-tetraethyldisilazane, or 1,2-diisopropyldisilazane, etc.; or a combination thereof, but not limited thereto.

[0196] The above surface modifier may be used as a solution diluted in an organic solvent. Here, the organic solvent may be an alcohol (organic solvent), and the surface modifier may be diluted to 1 to 15 volume% based on the total volume of the diluted solution.

[0197] In addition, the above surface modifier may be added in an amount of 0.01 to 90 volume% with respect to the wet gel composite for a sufficient surface modification effect, but is not limited thereto.

[0198] The surface modification step may be performed for 1 to 24 hours at a temperature of 50 to 90 ℃ or 50 to 80 ℃, but is not limited thereto.

[0199] drying stage

[0200] It may include a drying step of drying the surface-modified wet gel composite to obtain an aerogel composite.

[0201] The above drying is performed as a process that removes only the solvent while maintaining the pore structure of the aged gel, and can be performed, for example, by supercritical drying or atmospheric pressure drying.

[0202] The above supercritical drying process is performed using supercritical carbon dioxide. For example, a matured wet gel complex is placed into a supercritical drying reactor, and then liquid CO2 is filled and a solvent exchange process is performed to replace the alcohol solvent inside the wet gel with CO2. Afterward, the temperature is raised to 40 to 70 ℃ at a constant heating rate, e.g., 0.1 ℃ / min to 1 ℃ / min. Then, a pressure greater than the pressure at which carbon dioxide reaches a supercritical state, e.g. 100 bar to 150 bar, is maintained to maintain the carbon dioxide in a supercritical state for a certain period of time, specifically 20 minutes to 1 hour. Generally, carbon dioxide reaches a supercritical state at a temperature of 31 ℃ and a pressure of 73.8 bar. An aerogel composite can be manufactured by maintaining the carbon dioxide at a constant temperature and constant pressure for 2 to 12 hours, more specifically 2 to 6 hours, and then gradually removing the pressure to complete the supercritical drying process, but is not limited thereto.

[0203] In addition, the above atmospheric pressure drying process may be carried out according to conventional methods such as hot air drying or IR drying at a temperature of 70 to 200 ℃ and atmospheric pressure (1±0.3 atm), but is not limited thereto.

[0204] In addition to the above-described process, the preparation of the hydrogel involves acidifying a basic metal oxide precursor (e.g., sodium silicate) in water. Salt byproducts can be removed from the silicate precursor by ion exchange and / or by subsequently washing the formed gel with water. Removal of water from the pores of the gel can be carried out through exchange with a polar organic solvent, such as ethanol, methanol, or acetone. Subsequently, the liquid phase in the gel is at least partially extracted using innovative processing and extraction techniques.

[0205] In addition to the above-mentioned process, it includes reducing damaging capillary forces at the solvent / pore interface by chemically modifying the matrix material in a wet gel state through the conversion of surface hydroxyl groups to hydrophobic trimethylsilyl ether, thereby enabling liquid phase extraction from the gel material at temperatures and pressures below the critical point of the solvent.

[0206] In addition to the above-described process, the liquid (solvent) within the gel material may be frozen at a lower temperature and subsequently subjected to a sublimation process to remove the solvent from the gel material. Such removal or drying of the solvent from the gel material is understood to be within the scope of the present disclosure. Such removal largely preserves the gel structure, thereby producing an aerogel with unique properties.

[0207] The aerogel composite provided in the present invention can be usefully used as an insulating material, thermal insulation material, or non-combustible material for various industrial facilities such as piping or industrial furnaces, as well as for thermal insulation plant facilities, aircraft, ships, automobiles, electronic devices, batteries, etc.

[0209] According to another embodiment of the present invention, the invention relates to an insulating member comprising an aerogel composite provided in the present invention.

[0210] The above-described insulating member may include the aerogel composite described above and a supporting member located on at least one of the upper and lower surfaces of the aerogel composite.

[0211] Examples of the above-mentioned support members include film-type support members, sheet-type support members, thin-film support members, porous support members, etc.

[0212] The above film-like support member is formed by molding a polymer raw material into a thin film, and examples include organic films such as PET and polyimide, glass films, etc. (metal deposition films are also included).

[0213] The above sheet-like support member is formed from organic, inorganic, or metal fiber-like raw materials, and examples include paper, non-woven fabric (including glass mats), organic fiber fabric, glass cloth, etc.

[0214] The above-mentioned thin film support member is formed by molding a metal raw material into a thin film, and examples include aluminum foil, copper foil, etc.

[0215] The above porous support member has a porous structure made of organic, inorganic, or metal raw materials, and examples include porous organic materials (e.g., polyurethane foam), porous inorganic materials (e.g., zeolite sheets), porous metal materials (e.g., porous metal sheets, porous aluminum sheets), etc.

[0216] The thickness of the above-mentioned support member is not particularly limited and may be, for example, 0.1 to 100 μm, or 1 to 50 μm.

[0217] In the present invention, the thermal insulation member can also be applied for use as a thermal insulation material, thermal insulation material, or non-combustible material in the construction field, aviation field, automotive field, battery, home appliance, semiconductor field, industrial equipment, etc.

[0219] The present invention will be explained in detail below through the following examples. However, the following examples are merely illustrative of the present invention, and the scope of the present invention is not limited by the following examples.

[0221] Examples

[0223] [Example 1]

[0224] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:6 with the hydrated TEOS solution. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the sol was passed through a fiber (glass fiber mat, 10 mm) as a substrate to infiltrate the fiber with the catalyzed sol, ensuring that the catalyzed silica sol was impregnated into the fiber mat in a volume ratio of 1:1 (catalyzed silica sol: fiber). Fibers infiltrated with a catalytic sol after passing through an impregnation tank were gelled for about 10 minutes while passing over a conveyor belt at a constant speed. During this time, the ambient temperature on the conveyor belt was maintained at 35°C. Subsequently, a solution of 2.9 wt% methyltriethoxysilane (MTES) diluted in ethanol with a moisture content of 10 wt% was added to the gelled wet gel composite at 109 wt% based on the volume of the wet gel composite as an aging solution, and aging was carried out at a temperature of 75°C for 1 hour. After aging, a hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added as a surface modifier at 90 wt% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75°C for 4 hours. Subsequently, supercritical drying was performed under conditions of 150 bar and 70 ℃ in CO2 to produce an aerogel composite with a density of approximately 0.177 g / cc.

[0226] [Example 2]

[0227] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:4 with the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalytic sol into an impregnation tank, the catalytic sol was passed through a fiber (glass fiber mat, 10 mm) as a substrate to infiltrate the fiber, such that the catalytic silica sol impregnated the fiber mat in a volume ratio of 0.7:1 (catalytic silica sol: fiber). Fibers infiltrated with a catalytic sol after passing through an impregnation tank were gelled for about 10 minutes while passing over a conveyor belt at a constant speed. During this time, the ambient temperature on the conveyor belt was maintained at 40°C. Subsequently, a solution of 2.9 wt% methyltriethoxysilane (MTES) diluted in ethanol with a moisture content of 10 wt% was added to the gelled wet gel composite at 109 volume% based on the volume of the wet gel composite as an aging solution, and aging was carried out at a temperature of 75°C for 1 hour. After aging, a hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added as a surface modifier at 90 volume% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75°C for 4 hours. Subsequently, supercritical drying was performed under conditions of 150 bar and 70 ℃ in CO2 to produce an aerogel composite with a density of approximately 0.187 g / cc.

[0229] [Example 3]

[0230] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and TEOS in a molar ratio of 97:3. A silica sol was prepared by mixing the silica precursor composition with water in a molar ratio of 1:10 and adding ethanol in a weight ratio of 1:2 with the silica precursor composition. Hydrochloric acid was added to lower the pH of the silica sol to 3 or lower to promote hydrolysis. A base catalyst solution (10 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol was added to prepare a catalyzed silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 5 mm) as a substrate, ensuring that the catalyzed silica sol was impregnated into the fiber mats at a volume ratio of 0.5:1 (catalyzed silica sol: fiber). The fibers infiltrated with the catalyzed sol after passing through the impregnation tank were gelled while moving along a conveyor belt at a constant speed for approximately 10 minutes. At this time, the ambient temperature on the conveyor belt was maintained at 35°C. Subsequently, a solution of ammonia water diluted in ethanol (2.4 wt%) was added to the gelled wet gel composite at 109% based on the volume of the wet gel composite, and aging was carried out at a temperature of 75°C for 1 hour. After aging, a hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added as a surface modifier at 90 volume% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75°C for 4 hours. Subsequently, supercritical drying was performed under conditions of CO2 150 bar and 70°C to produce an aerogel composite with a density of approximately 0.170 g / cc.

[0232] [Example 4]

[0233] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and TEOS in a molar ratio of 97:3. A silica sol was prepared by mixing the silica precursor composition with water in a molar ratio of 1:10 and adding ethanol in a weight ratio of 1:2 with the silica precursor composition. Hydrochloric acid was added to lower the pH of the silica sol to 3 or lower to promote hydrolysis. A catalyzed silica sol was prepared by adding a base catalyst solution (10 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 5 mm) as a substrate, ensuring that the catalyzed silica sol was impregnated into the fiber mats at a volume ratio of 0.7:1 (catalyzed silica sol: fiber). The fibers infiltrated with the catalyzed sol after passing through the impregnation tank were gelled while moving along a conveyor belt at a constant speed for approximately 10 minutes. At this time, the ambient temperature on the conveyor belt was maintained at 40 ℃. Subsequently, a solution of ammonia water diluted in ethanol (2.4 wt%) was added to the gelled wet gel composite at 109% based on the volume of the wet gel composite, and aging was carried out at a temperature of 75 ℃ for 1 hour. After aging, a hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added as a surface modifier at 90 volume% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75 ℃ for 4 hours. Subsequently, supercritical drying was performed under conditions of CO2 150 bar and 70 ℃ to produce an aerogel composite with a density of approximately 0.190 g / cc.

[0235] [Example 5]

[0236] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and TEOS in a molar ratio of 97:3. A silica sol was prepared by mixing the silica precursor composition with water in a molar ratio of 1:10 and adding ethanol in a weight ratio of 1:2 with the silica precursor composition. Hydrochloric acid was added to lower the pH of the silica sol to 3 or lower to promote hydrolysis. A catalyzed silica sol was prepared by adding a base catalyst solution (10 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 5 mm) as a substrate, ensuring that the catalyzed silica sol was impregnated into the fiber mats at a volume ratio of 0.7:1 (catalyzed silica sol: fiber). The fibers infiltrated with the catalyzed sol after passing through the impregnation tank were gelled while moving along a conveyor belt at a constant speed for approximately 10 minutes. At this time, the ambient temperature on the conveyor belt was maintained at 40 ℃. Subsequently, a solution of 2.4 wt% trimethylethoxysilane (TMES) solution diluted in ethanol was added to the gelled wet gel composite as an aging solution at 109 vol% based on the volume of the wet gel composite, and aging was carried out at a temperature of 75 ℃ for 1 hour. After aging, a hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added as a surface modifier at 90 vol% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75 ℃ for 4 hours. Subsequently, supercritical drying was performed under conditions of CO2 150 bar and 70 ℃ to produce an aerogel composite with a density of approximately 0.211 g / cc.

[0238] [Example 6]

[0239] A silica precursor composition was prepared by mixing methyltriethoxysilane (MTES) and TEOS in a molar ratio of 97:3. A silica sol was prepared by mixing the silica precursor composition with water in a molar ratio of 1:10 and adding ethanol in a weight ratio of 1:2 with the silica precursor composition. Hydrochloric acid was added to lower the pH of the silica sol to 3 or lower to promote hydrolysis. A base catalyst solution (10 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol was added to prepare a catalyzed silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 5 mm) as a substrate, ensuring that the catalyzed silica sol impregnated the fiber mat in a volume ratio of 1:1 (catalyzed silica sol: fiber). The fibers infiltrated with the catalyzed sol after passing through the impregnation tank were gelled while moving along a conveyor belt at a constant speed for approximately 10 minutes. At this time, the ambient temperature on the conveyor belt was maintained at 35°C. Subsequently, a solution of 2.4 wt% trimethylethoxysilane (TMES) solution diluted in ethanol was added to the gelled wet gel composite as an aging solution at 109 volume% based on the volume of the wet gel composite, and aging was carried out at a temperature of 75°C for 1 hour. After aging, a hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added as a surface modifier at 90 volume% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75°C for 4 hours. Subsequently, supercritical drying was performed under conditions of CO2 150 bar and 70°C to produce an aerogel composite with a density of approximately 0.206 g / cc.

[0241] [Example 7]

[0242] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:4 with the hydrated TEOS solution. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the sol was passed through a fiber (glass fiber mat, 3 mm) as a substrate to infiltrate the fiber with the catalyzed sol, such that the catalyzed silica sol was impregnated into the fiber mat in a volume ratio of 0.7:1 (catalyzed silica sol: fiber). Fibers infiltrated with the catalytic sol after passing through an impregnation tank were gelled for approximately 10 minutes while moving along a conveyor belt at a constant speed. During this time, the ambient temperature on the conveyor belt was maintained at 35°C. After gelation was complete, the material was stabilized at room temperature (25°C) for 10 minutes, followed by primary aging in a 70°C oven for 50 minutes. Subsequently, a mixture of ethanol and ammonia water (volume ratio of 98:2) was prepared and added to the gelled wet gel composite in an amount 1.6 times the volume of the silica sol, followed by secondary aging in a 70°C oven for 1 hour. To the aged wet gel composite, a solution of trimethylethoxysilane (TMES) diluted in ethanol (2 vol%) was added at 90 vol% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75°C for 2 hours. Subsequently, supercritical drying was performed under conditions of 150 bar and 70 ℃ in CO2 to produce an aerogel composite with a density of approximately 0.189 g / cc.

[0244] [Example 8]

[0245] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:6 with the hydrated TEOS solution. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the sol was passed through a fiber (glass fiber mat, 3 mm) as a substrate to infiltrate the fiber with the catalyzed sol, such that the catalyzed silica sol was impregnated into the fiber mat in a volume ratio of 0.7:1 (catalyzed silica sol: fiber). Fibers infiltrated with a catalystd sol after passing through an impregnation tank were gelled for approximately 10 minutes while passing over a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 25°C. After gelation was complete, the fibers were stabilized at room temperature (25°C) for 10 minutes, followed by primary aging in a 70°C oven for 50 minutes. Subsequently, a solution of 2.9 wt% methyltriethoxysilane (MTES) diluted in ethanol with a moisture content of 10 wt% was prepared and added to the gelled wet gel composite at 109% of the volume of the wet gel composite, followed by secondary aging in a 75°C oven for 1 hour. To the aged wet gel composite, a solution of trimethylethoxysilane (TMES) diluted in ethanol (2 vol%) was added as a surface modifier at 90 vol% of the volume of the wet gel composite, and surface modification was performed at a temperature of 75°C for 2 hours. Subsequently, supercritical drying was performed under conditions of 150 bar and 70 ℃ of CO2 to produce an aerogel composite with a density of approximately 0.192 g / cc.

[0247] [Example 9]

[0248] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:6 with the hydrated TEOS solution. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. After filling 33.3 L of this catalyzed sol into an impregnation tank, the sol was passed through a fiber (glass fiber mat, 5 mm) as a substrate to infiltrate the fiber with the catalyzed sol, such that the catalyzed silica sol was impregnated into the fiber mat in a volume ratio of 0.7:1 (catalyzed silica sol: fiber). Fibers infiltrated with a catalytic sol after passing through an impregnation tank were gelled for about 10 minutes while passing over a conveyor belt at a constant speed. During this time, the ambient temperature on the conveyor belt was maintained at 35°C. After gelation was complete, the fibers were stabilized at room temperature (25°C) for 10 minutes, followed by primary aging in a 70°C oven for 50 minutes. Subsequently, a solution of 2.9 wt% methyltriethoxysilane (MTES) diluted in ethanol with a moisture content of 10 wt% was prepared and added to the gelled wet gel composite at 109% of the volume of the wet gel composite, followed by secondary aging in a 75°C oven for 1 hour. Afterward, supercritical drying was performed under conditions of CO2 150 bar and 70°C to produce an aerogel composite with a density of approximately 0.204 g / cc.

[0250] [Comparative Example 1]

[0251] A silica precursor composition was prepared by adding and mixing fully hydrolyzed TEOS (silica content: 20 wt%, HTEOS), ethanol, and distilled water in a weight ratio of 1:2:0.22, respectively. A catalyst composition was prepared by adding and mixing ethanol, NaOH (5 wt% aqueous solution), and trimethylethoxysilane (TMES) in a weight ratio of 1:0.3:1, respectively. A catalyzed silica sol was prepared by mixing the prepared silica precursor composition and the catalyst composition in a volume ratio of 9:1 in a reactor. The catalyzed sol was infiltrated into the fibers by passing them through a fiber (glass fiber mat, 10 mm) as a substrate, wherein the catalyzed silica sol was impregnated in a volume ratio of 1:1 (catalyzed silica sol:glass fiber mat) relative to the volume of the glass fiber mat, and gelled for about 10 minutes to prepare a wet gel composite. Fibers infiltrated with a catalyzed sol after passing through an impregnation tank were left at room temperature for 24 hours to undergo gelation, aging, and surface modification. Subsequently, supercritical drying was performed under conditions of 150 bar CO2 and 70 ℃ to produce an aerogel composite with a density of approximately 0.206 g / cc.

[0253] [Comparative Example 2]

[0254] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:4 with the hydrated TEOS solution. A catalytic sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. The catalytic sol was impregnated into a fiber (glass fiber mat, 10 mm) by passing it through the fiber as a substrate, wherein the catalytic silica sol was impregnated at a volume ratio of 0.3:1 (catalytic silica sol:glass fiber mat) relative to the volume of the glass fiber mat. Fibers infiltrated with a catalytic sol after passing through an impregnation tank were gelled for about 10 minutes while passing over a conveyor belt at a constant speed. During this time, the ambient temperature on the conveyor belt was maintained at 35°C. Afterward, the gelled wet gel composite was aged by leaving it in a chamber at 70°C for 24 hours. A hexamethyldisilazane (HMDS) / ethanol solution (5:95 volume ratio) was added to the aged wet gel composite as a surface modifier at 90 volume% based on the volume of the wet gel composite, and surface modification was performed at a temperature of 75°C for 4 hours. Subsequently, supercritical drying was performed under conditions of CO2 150 bar and 70°C to produce an aerogel composite with a density of about 0.142 g / cc.

[0256] [Comparative Example 3]

[0257] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:4 with the hydrated TEOS solution. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the silica sol. The catalyzed sol was impregnated into the fiber by passing it through a fiber (glass fiber mat, 3 mm) as a substrate, wherein the catalyzed silica sol was impregnated at a volume ratio of 0.5:1 (catalyzed silica sol:glass fiber mat) relative to the volume of the glass fiber mat. Fibers infiltrated with a catalytic sol after passing through an impregnation tank were gelled at room temperature for about 10 minutes while passing over a conveyor belt at a constant speed. After gelation was complete, the fibers were stabilized at room temperature (25°C) for 10 minutes, followed by primary aging in a 70°C oven for 50 minutes. Subsequently, a mixture of ethanol and ammonia water (volume ratio of 98:2) was prepared and added to the gelled wet gel composite in an amount 1.6 times the volume of the silica sol, followed by secondary aging in a 70°C oven for 1 hour. Afterward, supercritical drying was performed under conditions of CO2 150 bar and 70°C to produce an aerogel composite with a density of approximately 0.168 g / cc.

[0259] [Experimental Example 1] Measurement of Distribution by Density and Pore Size

[0260] 1. Density

[0261] For each silica aerogel composite prepared in each example and comparative example, five specimens measuring 10 cm x 10 cm were prepared, and their weights were measured. The thickness of each specimen was measured using a NETZSCH HFM436 instrument. The density was calculated based on the measured weight, thickness, and size, and the average density of the five specimens was determined as the final density. The results are shown in Table 1 below.

[0262] 2. Volume ratio of effective pores with a diameter of 30 nm or less (%)

[0263] For each silica aerogel composite prepared in each example and comparative example, the partial pressure (0.11) was measured using a Micrometrics ASAP 2010 instrument. <p / p0<1)에 따른 질소의 흡 / 탈착량으로 분석하여, 비표면적, 기공 부피 및 기공 직경을 측정하였다. 측정된 기공 부피에서 기공 직경이 30 nm 이하의 수치범위를 갖는 기공(유효 기공)의 부피 비율을 산출하여 그 결과를 하기 표 1에 나타내었다.

[0264] division Density (g / cc) Effective pore volume ratio (%) Example 1 0.177 35.6 Example 2 0.187 31.1 Example 3 0.170 40.2 Example 4 0.190 38.7 Example 5 0.211 33.8 Example 6 0.206 37.2 Example 7 0.189 30.3 Example 8 0.192 37.3 Example 9 0.204 38.1 Comparative Example 1 0.206 22.0 Comparative Example 2 0.142 20.9 Comparative Example 3 0.168 20.1

[0266] [Experimental Example 2] Measurement of Recovery Rate and Thermal Transmittance of Aerogel Composite After Compression

[0267] 1. Compression recovery rate

[0268] Specimens measuring 20 cm x 20 cm were prepared using the aerogel composites obtained in each example and comparative example. In cases where the width or length of the prepared aerogel composite was smaller than 20 cm, two or more specimens may be arranged in parallel adjacent to each other to achieve a specimen size of 20 cm x 20 cm, after which measurements may be performed on such specimens. Each prepared specimen was compressed for 10 minutes under each pressure condition using a QMESYS QM900A-15T press machine. The thickness of the aerogel composite was measured using a Netzsch HFM436 machine before compression and after 1 hour had elapsed since the end of compression. The compression recovery rate was calculated according to Equation 1 below, and the results are shown in Table 2 below. Note that the pressure values ​​shown in Table 2 below represent the pressure applied per unit area of ​​the specimen, and refer to the value obtained by dividing the area of ​​the specimen by the area of ​​the cylinder of the press machine multiplied by the set pressure value as shown in Equation 2 below. The cylinder radius of the QM900A-15T press machine used in this experiment is 6.25 cm, and the cylinder size is 12.5 cm.

[0269] [Equation 1]

[0270] Compression recovery rate (%) = {(Cross-sectional thickness of aerogel composite after compression) / (Cross-sectional thickness of aerogel composite before compression)} X 100

[0271] [Equation 2]

[0272] Actual pressure value = (Inner diameter radius of press cylinder (cm) X Inner diameter radius of press cylinder (cm) X 3.14 X Set pressure value) / (Area of ​​specimen (cm²) 2 ))

[0273] 2. Thermal transmittance

[0274] After conducting the experiment in the same manner as in 1 above, the thermal conductivity of the aerogel composite was measured using a Netzsch HFM436 instrument before compression and after 1 hour had elapsed after the compression was finished, the thermal transmittance was calculated, and the rate of increase in thermal transmittance compared to before compression was evaluated, and the results are shown in Table 3 below.

[0275] In addition, to check the change in thermal transmittance before and after compression, the average value (b) of the thermal transmittance measured after compression at pressures of no compression (0 bar), 3 bar, 9 bar, and 24 bar was calculated, and as shown in Equation 3 below, the difference between the thermal transmittance (a) measured after compression at pressures of 0 bar, 3 bar, 9 bar, and 24 bar and the average value (b) of these thermal transmittances, and the value A, which is the difference divided by the average value (b) of the thermal transmittance, were calculated, and the results are shown in Table 4.

[0276] [Equation 3]

[0277] {(Thermal transmittance before and after compression (a)) - (Average value of thermal transmittances before and after compression (b))} = (Average value of thermal transmittances before and after compression (b)) XA

[0278] In addition, to check the change in thermal transmittance after compression, the average value (d) of the thermal transmittance measured after compression at pressures of 3 bar, 9 bar, and 24 bar was calculated, and the difference between the thermal transmittance (c) measured after compression at pressures of 3 bar, 9 bar, or 24 bar and the average value (d), and B, which is the difference divided by the average value (d) of the thermal transmittance, were calculated as shown in Equation 4 below, and the results are shown in Table 5.

[0279] [Equation 4]

[0280] (Thermal transmittance after compression (c) - Average thermal transmittance after compression (d)) = (Average thermal transmittance after compression (d)) XB

[0281] Each result value shown in Tables 2 to 5 below was rounded to the second decimal place.

[0282] division Pressure conditions Thickness after compression (mm) Compression recovery rate (%) Example 1 - 10.4 - 3 bar, 10 min 9.1 87.50 9 bar, 10 min 8.2 78.85 15 bar, 10 min 8.0 76.92 24 bar, 10 min 8.1 77.88 30 bar, 10 min 7.9 75.96 33 bar, 10 min 8.0 76.92 Example 2 - 8.6 - 3 bar, 10 min 8.2 95.35 9 bar, 10 min 8.0 93.02 15 bar, 10 min 7.9 91.86 24 bar, 10 min 7.7 89.53 30 bar, 10 min 7.4 86.05 33 bar, 10 min 6.9 80.23 Example 3 - 3.6 - 3 bar, 10 min 3.4 94.44 9 bar, 10 min 3.3 91.67 15 bar, 10 min 3.2 88.89 24 bar, 10 min 3.2 88.89 30 bar, 10 min 3.1 86.11 33 bar, 10 min 3.0 83.33 Example 4 - 4.6 - 3 bar, 10 min 4.4 95.65 9 bar, 10 min 4.4 95.65 15 bar, 10 min 4.2 91.30 24 bar, 10 min 4.1 89.13 30 bar, 10 min 4.0 86.96 33 bar, 10 min 3.9 84.78 Example 5 - 4.7 - 3 bar, 10 min 4.6 97.87 9 bar, 10 min 4.2 89.36 15 bar, 10 min 4.2 89.36 24 bar, 10 min 4.1 87.23 30 bar, 10 min 4.1 87.23 33 bar, 10 min 4.0 85.11 Example 6 - 5.0 - 3 bar, 10 min 4.6 92.00 9 bar, 10 min 3.9 78.00 15 bar, 10 min 3.7 74.00 24 bar, 10 min 3.7 74.00 30 bar, 10 min 3.6 72.00 33 bar, 10 min 3.6 72.00 Example 7 - 2.7 - 3 bar, 10 min 2.6 96.30 9 bar, 10 min 2.5 92.59 15 bar, 10 min 2.5 92.59 24 bar, 10 min 2.4 88.89 30 bar, 10 min 2.3 85.19 33 bar, 10 min 2.3 85.19 Example 8 - 2.7 - 3 bar, 10 min 2.7 100.00 9 bar, 10 min 2.6 96.30 15 bar, 10 min 2.6 96.30 24 bar, 10 min 2.5 92.59 30 bar, 10 min 2.5 92.59 33 bar, 10 min 2.4 88.89 Example 9 - 3.9 100.00 3 bar, 10 min 3.5 89.74 9 bar, 10 min 3.1 79.49 15 bar, 10 min 3.0 76.92 24 bar, 10 min 2.9 74.36 30 bar, 10 min 2.9 74.36 33 bar, 10 min 2.8 71.79 Comparative Example 1 - 9.5 - 3 bar, 10 min 6.0 63.16 9 bar, 10 min 5.0 52.63 15 bar, 10 min 4.8 50.53 24 bar, 10 min 4.7 49.47 30 bar, 10 min 4.9 51.58 33 bar, 10 min 5.0 52.63 Comparative Example 2 - 6.3 - 3 bar, 10 min 4.4 69.84 9 bar, 10 min 3.7 58.73 15 bar, 10 min 3.3 52.38 24 bar, 10 min 3.1 49.21 30 bar, 10 min 2.9 46.03 33 bar, 10 min 2.9 46.03 Comparative Example 3 - 2.6 - 3 bar, 10 min 1.7 65.38 9 bar, 10 min 1.5 57.69 15 bar, 10 min 1.4 53.85 24 bar, 10 min 1.1 42.31 30 bar, 10 min 1.0 38.46 33 bar, 10 min 0.9 34.62

[0283] division Pressure conditions Thermal transmittance (W / m²) 2 K) Thermal transmittance growth rate (times) Example 1 - 2.26 - 3 bar, 10 min 2.59 1.15 9 bar, 10 min 2.89 1.28 15 bar, 10 min 3.05 1.35 24 bar, 10 min 3.09 1.37 30 bar, 10 min 3.19 1.41 33 bar, 10 min 3.24 1.43 Example 2 - 2.42 - 3 bar, 10 min 2.55 1.05 9 bar, 10 min 2.66 1.10 15 bar, 10 min 2.75 1.14 24 bar, 10 min 2.87 1.19 30 bar, 10 min 3.04 1.26 33 bar, 10 min 3.29 1.36 Example 3 - 6.42 - 3 bar, 10 min 6.85 1.07 9 bar, 10 min 7.18 1.12 15 bar, 10 min 7.44 1.16 24 bar, 10 min 7.47 1.16 30 bar, 10 min 7.74 1.21 33 bar, 10 min 8.07 1.26 Example 4 - 4.30 - 3 bar, 10 min 4.55 1.06 9 bar, 10 min 4.66 1.08 15 bar, 10 min 5.14 1.19 24 bar, 10 min 5.29 1.23 30 bar, 10 min 5.53 1.28 33 bar, 10 min 5.72 1.33 Example 5 - 4.26 - 3 bar, 10 min 4.43 1.04 9 bar, 10 min 4.93 1.16 15 bar, 10 min 4.98 1.17 24 bar, 10 min 5.12 1.20 30 bar, 10 min 5.15 1.21 33 bar, 10 min 5.33 1.25 Example 6 - 3.16 - 3 bar, 10 min 3.48 1.10 9 bar, 10 min 4.49 1.42 15 bar, 10 min 4.92 1.56 24 bar, 10 min 4.89 1.55 30 bar, 10 min 5.00 1.58 33 bar, 10 min 5.39 1.71 Example 7 - 6.93 - 3 bar, 10 min 7.27 1.05 9 bar, 10 min 7.60 1.10 15 bar, 10 min 7.60 1.10 24 bar, 10 min 7.96 1.15 30 bar, 10 min 8.30 1.20 33 bar, 10 min 8.39 1.21 Example 8 - 8.85 - 3 bar, 10 min 8.89 1.00 9 bar, 10 min 9.23 1.04 15 bar, 10 min 9.27 1.05 24 bar, 10 min 9.88 1.12 30 bar, 10 min 10.00 1.13 33 bar, 10 min 10.46 1.18 Example 9 - 6.44 1.00 3 bar, 10 min 6.75 1.05 9 bar, 10 min 7.73 1.20 15 bar, 10 min 8.02 1.25 24 bar, 10 min 8.29 1.29 30 bar, 10 min 8.48 1.32 33 bar, 10 min 8.89 1.38 Comparative Example 1 - 1.84 - 3 bar, 10 min 2.73 1.48 9 bar, 10 min 3.44 1.87 15 bar, 10 min 4.38 2.38 24 bar, 10 min 5.64 3.07 30 bar, 10 min 5.57 3.03 33 bar, 10 min 5.65 3.07 Comparative Example 2 - 3.89 - 3 bar, 10 min 6.09 1.57 9 bar, 10 min 8.51 2.19 15 bar, 10 min 9.97 2.56 24 bar, 10 min 10.94 2.81 30 bar, 10 min 11.76 3.02 33 bar, 10 min 11.83 3.04 Comparative Example 3 - 9.38 - 3 bar, 10 min 16.29 1.74 9 bar, 10 min 20.73 2.21 15 bar, 10 min 23.00 2.45 24 bar, 10 min 29.55 3.15 30 bar, 10 min 33.10 3.53 33 bar, 10 min 36.89 3.93

[0284] division Pressure conditions Thermal transmittance (a) (W / m²) before and after compression 2 K) Average value of thermal transmittances before and after compression (b) (W / m²) 2 K) Deviation in thermal transmittance before and after compression (ab) (W / m 2 K) Deviation in thermal transmittance before and after compression / Average thermal transmittance (ab / b = A) Example 1 0 bar, 10 min 2.26 2.71 -0.45 -0.17 3 bar, 10 min 2.59 -0.12 -0.04 9 bar, 10 min 2.89 0.18 0.07 24 bar, 10 min 3.09 0.38 0.14 Example 2 0 bar, 10 min 2.42 2.63 -0.21 -0.08 3 bar, 10 min 2.55 -0.08 -0.03 9 bar, 10 min 2.66 0.03 0.01 24 bar, 10 min 2.87 0.24 0.09 Example 3 0 bar, 10 min 6.42 6.98 -0.56 -0.08 3 bar, 10 min 6.85 -0.13 -0.02 9 bar, 10 min 7.18 0.20 0.03 24 bar, 10 min 7.47 0.49 0.07 Example 4 0 bar, 10 min 4.30 4.70 -0.40 -0.08 3 bar, 10 min 4.55 -0.15 -0.03 9 bar, 10 min 4.66 -0.04 -0.01 24 bar, 10 min 5.29 0.59 0.13 Example 5 0 bar, 10 min 4.26 4.69 -0.43 -0.09 3 bar, 10 min 4.43 -0.26 -0.05 9 bar, 10 min 4.93 0.24 0.05 24 bar, 10 min 5.12 0.43 0.09 Example 6 0 bar, 10 min 3.16 4.01 -0.85 -0.21 3 bar, 10 min 3.48 -0.53 -0.13 9 bar, 10 min 4.49 0.48 0.12 24 bar, 10 min 4.89 0.88 0.22 Example 7 0 bar, 10 min 6.93 7.44 -0.51 -0.07 3 bar, 10 min 7.27 -0.17 -0.02 9 bar, 10 min 7.60 0.16 0.02 24 bar, 10 min 7.96 0.52 0.07 Example 8 0 bar, 10 min 8.85 9.21 -0.36 -0.04 3 bar, 10 min 8.89 -0.32 -0.03 9 bar, 10 min 9.23 0.02 0.00 24 bar, 10 min 9.88 0.67 0.07 Example 9 0 bar, 10 min 6.44 7.30 -0.86 -0.12 3 bar, 10 min 6.75 -0.55 -0.08 9 bar, 10 min 7.73 0.43 0.06 24 bar, 10 min 8.29 0.99 0.14 Comparative Example 1 0 bar, 10 min 1.84 3.41 -1.57 -0.46 3 bar, 10 min 2.73 -0.68 -0.20 9 bar, 10 min 3.44 0.03 0.01 24 bar, 10 min 5.64 2.23 0.65 Comparative Example 2 0 bar, 10 min 3.89 7.36 -3.47 -0.47 3 bar, 10 min 6.09 -1.27 -0.17 9 bar, 10 min 8.51 1.15 0.16 24 bar, 10 min 10.94 3.58 0.49 Comparative Example 3 0 bar, 10 min 9.38 18.99 -9.61 -0.51 3 bar, 10 min 16.29 -2.70 -0.14 9 bar, 10 min 20.73 1.74 0.09 24 bar, 10 min 33.10 10.56 0.56

[0285] division Pressure conditions Thermal transmittance after compression (c) (W / m²) 2 K) Average thermal transmittance after compression (d) (W / m²) 2 K) Deviation (cd) of thermal transmittances after compression (W / m²) 2 K) Deviation in thermal transmittance after compression / Average thermal transmittance (cd / d = B) Example 1 3 bar, 10 min 2.59 2.86 -0.27 -0.09 9 bar, 10 min 2.89 0.03 0.01 24 bar, 10 min 3.09 0.23 0.08 Example 2 3 bar, 10 min 2.55 2.69 -0.14 -0.05 9 bar, 10 min 2.66 -0.03 -0.01 24 bar, 10 min 2.87 0.18 0.07 Example 3 3 bar, 10 min 6.85 7.17 -0.32 -0.04 9 bar, 10 min 7.18 0.01 0.00 24 bar, 10 min 7.47 0.30 0.04 Example 4 3 bar, 10 min 4.55 4.83 -0.28 -0.06 9 bar, 10 min 4.66 -0.17 -0.04 24 bar, 10 min 5.29 0.46 0.10 Example 5 3 bar, 10 min 4.43 4.83 -0.40 -0.08 9 bar, 10 min 4.93 0.10 0.02 24 bar, 10 min 5.12 0.29 0.06 Example 6 3 bar, 10 min 3.48 4.29 -0.81 -0.19 9 bar, 10 min 4.49 0.20 0.05 24 bar, 10 min 4.89 0.60 0.14 Example 7 3 bar, 10 min 7.27 7.61 -0.34 -0.04 9 bar, 10 min 7.60 -0.01 0.00 24 bar, 10 min 7.96 0.35 0.05 Example 8 3 bar, 10 min 8.89 9.33 -0.44 -0.05 9 bar, 10 min 9.23 -0.10 -0.01 24 bar, 10 min 9.88 0.55 0.06 Example 9 3 bar, 10 min 6.75 7.59 -0.84 -0.11 9 bar, 10 min 7.73 0.14 0.02 24 bar, 10 min 8.29 0.70 0.09 Comparative Example 1 3 bar, 10 min 2.73 3.94 -1.21 -0.31 9 bar, 10 min 3.44 -0.50 -0.13 24 bar, 10 min 5.64 1.70 0.43 Comparative Example 2 3 bar, 10 min 6.09 8.51 -2.42 -0.28 9 bar, 10 min 8.51 0.00 0.00 24 bar, 10 min 10.94 2.43 0.29 Comparative Example 3 3 bar, 10 min 16.29 22.19 -5.90 -0.27 9 bar, 10 min 20.73 -1.46 -0.07 24 bar, 10 min 29.55 7.36 0.33

[0286] As shown in Tables 2 to 5 above, it was confirmed that the aerogel composites of Examples 1 to 9 prepared according to the present invention had a higher compression recovery rate compared to the aerogel composites of Comparative Examples 1 to 3. It was also confirmed that the degree of increase in the thermal transmittance of the aerogel composite after compression was small compared to before compression, and that even when compressed at various pressure values ​​ranging from low to high pressure, the degree of change in thermal transmittance was small and the thermal insulation performance was maintained at an excellent level. From these results, it was confirmed that the aerogel composite of the present invention has excellent pore elasticity, flexibility, and strength, and thus has excellent recovery power even after high-pressure compression. Accordingly, a rapid decrease in thermal insulation performance due to pore destruction, particularly pore destruction of a size of 30 nm or less, is prevented, and excellent thermal insulation performance is maintained even after compression.

[0288] Foregoing, specific parts of the present invention have been described in detail. It is evident to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the invention. Accordingly, the actual scope of the invention is defined by the appended claims and their equivalents.

Claims

Claim 1 Fiber substrate; An aerogel composite comprising an aerogel having one or more pores, wherein the aerogel composite has a flat shape, and when the aerogel composite is compressed by applying pressures of 3 bar, 9 bar, and 24 bar, respectively, in the transverse direction with respect to the cross-section of the aerogel composite, the thermal transmittance after compression is 1.8 times or less compared to the thermal transmittance before compression along the transverse direction, and the thermal transmittance of the aerogel composite satisfies the following Equation 3: [Equation 3] {(Thermal transmittance before and after compression (a)) - (Average value of thermal transmittances before and after compression (b))} = (Average value of thermal transmittances before and after compression (b)) XA In the above Equation 3, the thermal transmittance before and after compression (a) is the thermal transmittance obtained after compression with 0 bar, 3 bar, 9 bar, or 24 bar in the transverse direction with respect to the cross-section of the aerogel composite, and the average value of thermal transmittances before and after compression (b) is It refers to the average value of the thermal transmittances obtained after compression with pressure values ​​of 0 bar, 3 bar, 9 bar, and 24 bar, respectively, in the transverse direction with respect to the cross-section of the aerogel composite, and A is a rational number from -0.25 to +0.

25. Claim 2 An aerogel composite according to claim 1, wherein when a pressure of 3 bar is applied in the transverse direction to the cross-section of the aerogel composite, the heat transfer coefficient after compression is 1.45 times or less compared to the heat transfer coefficient before compression along the transverse direction. Claim 3 An aerogel composite according to claim 1, wherein the compression recovery rate expressed by the following Equation 1 is 60% or more when pressures of 3 bar, 9 bar, and 24 bar, respectively, are applied transversely to the cross-section of the aerogel composite: [Equation 1] Compression recovery rate (%) = {(Cross-sectional thickness of the aerogel composite after compression) / (Cross-sectional thickness of the aerogel composite before compression)} X 100 Claim 4 In claim 1, the thermal transmittance obtained after compression with a pressure of 3 bar, 9 bar, and 24 bar, respectively, in the transverse direction with respect to the cross-section of the aerogel composite satisfies the following Equation 4: [Equation 4] (thermal transmittance after compression (c) - average value of thermal transmittances after compression (d)) = (average value of thermal transmittances after compression (d)) XB. In the above Equation 4, the thermal transmittance after compression (c) refers to the thermal transmittance obtained after compression with a pressure of 3 bar, 9 bar, or 24 bar, respectively, in the transverse direction with respect to the cross-section of the aerogel composite, and the average value of thermal transmittances after compression (d) refers to the average value of thermal transmittances obtained after compression by applying a pressure of 3 bar, 9 bar, and 24 bar, respectively, in the transverse direction with respect to the cross-section of the aerogel composite, and B is a rational number from -0.25 to +0.

25. Claim 5 In claim 1, the rate of change (C) of the thermal transmittance after compression per unit applied pressure, expressed by the following Equation 5 for the aerogel composite, is a rational number ranging from -0.100 to +0.100: [Equation 5] C = (thermal transmittance after compression at pressure x - thermal transmittance after compression at pressure y) / (x - y) In the above Equation 5, x and y are each independently different pressure values, which are any one of 3 bar, 9 bar, and 24 bar (unit bar). Claim 6 The aerogel composite according to claim 1, wherein the aerogel comprises pores having a pore diameter of 30 nm or less in an amount of 30% or more and 45% or less of the pore volume of the aerogel's skeletal structure. Claim 7 In claim 1, the density of the aerogel composite is 0.05 to 0.50 g / cm³ 3 Phosphorus, aerogel complex. Claim 8 In claim 1, the aerogel is an aerogel composite in which the aerogel is a silica aerogel. Claim 9 An aerogel composite according to paragraph 3, wherein the compression recovery rate represented by the above formula 1 is 60% to 99%. Claim 10 In claim 6, the aerogel composite having a pore diameter of 0.1 nm to 30 nm. Claim 11 The aerogel composite according to claim 1, wherein the heat transfer rate after compression is measured after 1 hour has elapsed after compression. Claim 12 In claim 8, the aerogel composite, wherein the heat transfer rate after compression is measured after 1 hour has elapsed after compression. Claim 13 An insulating member comprising the aerogel composite of claim 1. Claim 14 In claim 13, the insulating member further comprises a supporting member positioned on at least one of the upper and lower surfaces of the aerogel composite. Claim 15 delete

Citation Information

Patent Citations

  • Aerogel composite

    KR101928538B1

  • Method for preparing aerogel blanket and aerogel blanket prepared by the same

    KR101993643B1

  • Aerogel blanket

    KR1020210038375A

  • Method for preparing aerogel composite and aerogel composite

    KR1020220137360A

  • Thermally insulating substrate product and method of manufacture

    WO2022126279A1